Metal-loaded catalyst and manufacturing method thereof, and electrode and battery

JP2023129139A5Active Publication Date: 2025-02-28NISSHINBO IND INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022033945
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-03-04
Publication Date
2025-02-28
Estimated Expiration
2042-03-04

AI Technical Summary

Technical Problem

Conventional metal-supported catalysts face challenges in achieving both excellent durability and catalytic function while maintaining a high precious metal content.

Method used

A metal-supported catalyst is developed with a carbon support and catalytic metal particles containing a noble metal alloy, where the weight ratio of noble metal is 35% or more, and specific parameters such as alloy composition heterogeneity, half-value asymmetry, and quarter-value asymmetry are maintained to ensure both durability and catalytic efficiency.

Benefits of technology

The catalyst achieves high precious metal content with excellent durability and catalytic function, supported by a carbon structure optimized for effective noble metal alloy distribution and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2023129139000001
    Figure 2023129139000001
  • Figure 2023129139000002
    Figure 2023129139000002
  • Figure 2023129139000003
    Figure 2023129139000003
Patent Text Reader

Abstract

To provide a metal-loaded catalyst that, while having a large noble metal content, exhibits both an excellent durability and an excellent catalytic function and a manufacturing method thereof, as well as an electrode and a battery.SOLUTION: A metal-loaded catalyst comprises a carbon support and noble metal alloy-containing catalyst metal particles supported by the carbon support. The ratio of the weight of the noble metal to the weight of the metal-loaded catalyst is 35 wt.% or more. The metal-loaded catalyst has the following property (a) and / or property (b): (a) the alloy composition heterogeneity is at most 0.55; and (b) the half-maximum asymmetry and the 1 / 4-maximum asymmetry are both at most 0.55.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a metal-supported catalyst, a method for producing the same, and an electrode and a battery. [Background technology]

[0002] Patent Document 1 describes a catalyst for the air electrode of a polymer solid electrolyte fuel cell, wherein catalyst particles made by alloying platinum and one auxiliary metal are supported on a carbon powder carrier, the auxiliary metal being iron or cobalt, and the mixing ratio of platinum to the auxiliary metal being 6:1 to 3:2 (molar ratio).

[0003] Patent Document 2 describes an electrode catalyst for a fuel cell, comprising a solid carbon support and an alloy of platinum and cobalt supported on the support.

[0004] Patent Document 3 describes an electrode catalyst in which a catalytic metal is supported on a catalytic support, wherein the catalytic metal contains platinum and metal components other than platinum, has mesopores with a radius of 1 nm or more, the mode radius of the vacancy distribution of the mesopores is 1 nm or more and less than 2.5 nm, alloy fine particles of platinum and metal components other than platinum are supported in the mesopores, and the molar ratio of platinum to metal components other than platinum in the alloy fine particles supported in the mesopores is 1.0 to 10.0.

[0005] Patent Document 4 describes an electrode catalyst comprising a catalyst component containing alloy nanoparticles made of platinum and metal components other than platinum, supported on a catalyst support, wherein the catalyst support has mesopores with a radius of 1 nm or more, the mode radius of the vacancy distribution of the mesopores is 1 nm or more and less than 2.5 nm, at least a portion of the alloy nanoparticles are supported in the mesopores, and the measured value Q[Å] of the lattice constant of the alloy nanoparticles is smaller than the theoretical value P[Å] of the lattice constant according to Vegard's law, calculated by the following formula: Theoretical value P[Å] of lattice constant = (lattice constant of platinum - lattice constant of non-platinum metal atoms) × mole fraction of platinum atoms in the alloy nanoparticles + lattice constant of non-platinum metal atoms.

[0006] Patent Document 5 describes a method for producing an alloy catalyst, comprising: a first step of mixing a noble metal compound containing a noble metal element, a base metal compound containing a base metal element, a first solvent, and a porous material to obtain a mixture; a second step of fixing the noble metal compound and the base metal compound to the porous material by removing the first solvent from the mixture until the following formula "(volume of the first solvent in the mixture) ≤ (pore volume of the porous material) × 5" is satisfied; and a third step of contacting the porous material with a reducing solution containing a reducing agent having an oxidation-reduction potential of -1.20 V or less and a second solvent, wherein the amount of substance of the reducing agent in the reducing solution is 5 times or more the total amount of substance of the noble metal element. [Prior art documents] [Patent Documents]

[0007] [Patent Document 1] Japanese Patent Publication No. 2003-142112 [Patent Document 2] International Publication No. 2016 / 063968 [Patent Document 3] International Publication No. 2017 / 183475 [Patent Document 4] Japanese Patent Publication No. 2018-116815 [Patent Document 5] Japanese Patent Publication No. 2020-171917 [Overview of the Initiative] [Problems that the invention aims to solve]

[0008] However, conventionally, it has been difficult to create a metal-supported catalyst that possesses a high precious metal content while also exhibiting excellent durability and superior catalytic function.

[0009] This invention has been made in view of the above problems, and one of its objectives is to provide a metal-supported catalyst that has a large precious metal content while possessing excellent durability and excellent catalytic function, as well as a method for producing the same, and an electrode and a battery. [Means for solving the problem]

[0010] A metal-supported catalyst according to one embodiment of the present invention for solving the above problems is a metal-supported catalyst comprising a carbon carrier and catalyst metal particles containing a noble metal alloy supported on the carbon carrier, wherein the ratio of the weight of the noble metal to the weight of the metal-supported catalyst is 35% by weight or more, and has the following characteristics (a) and / or (b): (a) The alloy composition heterogeneity calculated by the following formula (I) is 0.55 or less; JPEG2023129139000001.jpg11170 (In equation (I) above, the theoretical lattice constant and the experimentally measured lattice constant are the theoretical lattice constant and the experimentally measured lattice constant of the aforementioned precious metal alloy, respectively.) (b) The half-value asymmetry and quarter-value asymmetry calculated by equations (II) and (III) below are both 0.55 or less; JPEG2023129139000002.jpg11170JPEG2023129139000003.jpg10170(In the above formulas (II) and (III), D m D is the value of the diffraction angle 2θ in which the diffraction line shows maximum intensity within the range of diffraction angle 2θ in which the diffraction peak of the (111) plane of the noble metal alloy appears in the X-ray diffraction pattern obtained by powder X-ray diffraction, and Lh D is the smallest diffraction angle 2θ value among the diffraction angles 2θ in which the diffraction line exhibits half the intensity of the maximum intensity within the aforementioned range. HhD is the value of the largest diffraction angle 2θ among the diffraction angles 2θ in which the diffraction line exhibits half the intensity of the maximum intensity within the aforementioned range. Lq D is the smallest diffraction angle 2θ value among the diffraction angles 2θ in which the diffraction line exhibits an intensity of one-quarter of the maximum intensity within the aforementioned range. Hq is the value of the largest diffraction angle 2θ among the diffraction angles 2θ in which the diffraction line exhibits an intensity of one-quarter of the maximum intensity within the aforementioned range. ) According to the present invention, a metal-supported catalyst is provided that has a large precious metal content while possessing both excellent durability and excellent catalytic function.

[0011] The metal-supported catalyst may have characteristic (a). The metal-supported catalyst may also have characteristic (b). The metal-supported catalyst may have a number-average particle diameter of catalyst metal particles of 8.0 nm or less. The metal-supported catalyst may also have a volume-average particle diameter of catalyst metal particles of 8.0 nm or less.

[0012] An electrode according to one embodiment of the present invention for solving the above problems includes any of the above-mentioned metal-supported catalysts. According to the present invention, an electrode having excellent properties is provided.

[0013] A battery according to one embodiment of the present invention for solving the above problems includes the electrodes. According to the present invention, a battery having excellent characteristics is provided.

[0014] A method for manufacturing a metal-supported catalyst according to one embodiment of the present invention for solving the above problems is a method for manufacturing a metal-supported catalyst comprising a carbon carrier and catalyst metal particles containing a noble metal alloy supported on the carbon carrier, comprising: a first impregnation step of impregnating the carbon carrier with a precursor of a first metal, which is one of the noble metals and non-noble metals constituting the noble metal alloy; a first gas-phase reduction step of subjecting the carbon carrier impregnated with the precursor of the first metal to a gas-phase reduction treatment to obtain a first metal-supported catalyst supporting the first metal; a second impregnation step of impregnating the first metal-supported catalyst with a precursor of a second metal, which is the other of the noble metals and non-noble metals; and a second gas-phase reduction step of subjecting the first metal-supported catalyst impregnated with the precursor of the second metal to a gas-phase reduction treatment, and then to an alloying treatment to obtain a metal-supported catalyst on which catalyst metal particles containing an alloy of the first metal and the second metal are supported. According to the present invention, a method for manufacturing a metal-supported catalyst that has a large noble metal content while possessing excellent durability and excellent catalytic function is provided.

[0015] In the above method, the gas-phase reduction treatment may be a treatment of heating in a reducing atmosphere. The first impregnation step may include holding the solution containing the precursor of the first metal and the carbon support under reduced pressure, and / or the second impregnation step may include holding the solution containing the precursor of the second metal and the catalyst supported by the first metal under reduced pressure. The first impregnation step may also include holding the solution containing the precursor of the first metal and the carbon support under pressure, and / or the second impregnation step may include holding the solution containing the precursor of the second metal and the catalyst supported by the first metal under pressure.

[0016] Furthermore, the first impregnation step may include first holding the solution containing the precursor of the first metal and the carbon support under reduced pressure, and then holding it under pressure, and / or the second impregnation step may include first holding the solution containing the precursor of the second metal and the first metal-supported catalyst under reduced pressure, and then holding it under pressure. Furthermore, the first impregnation step may include holding the solution containing the precursor of the first metal and the carbon support at a temperature of 5°C or lower, and / or the second impregnation step may include holding the solution containing the precursor of the second metal and the first metal-supported catalyst at a temperature of 5°C or lower. [Effects of the Invention]

[0017] According to the present invention, metal-supported catalysts, electrodes, and batteries are provided that have a large precious metal content while possessing excellent durability and excellent catalytic function. [Brief explanation of the drawing]

[0018] [Figure 1] This diagram illustrates an example of the results of analyzing the Raman spectrum obtained by Raman spectroscopy of a metal-supported catalyst in an embodiment of this theory. [Figure 2] This is an explanatory diagram showing a typical X-ray diffraction pattern obtained by powder X-ray diffraction of a metal-supported catalyst. [Figure 3A] This is an explanatory diagram showing an example of the results of analyzing the X-ray diffraction pattern obtained by powder X-ray diffraction of the metal-supported catalyst in the embodiment of this product. [Figure 3B] This is an explanatory diagram showing another example of the results of analyzing the X-ray diffraction pattern obtained by powder X-ray diffraction of the metal-supported catalyst in the embodiment of this present invention. [Figure 4A] This is an explanatory diagram showing an example of the results of analyzing the X-ray diffraction pattern obtained by powder X-ray diffraction of the metal-supported catalyst in the embodiment of this product. [Figure 4B] This is an explanatory diagram showing another example of the results of analyzing the X-ray diffraction pattern obtained by powder X-ray diffraction of the metal-supported catalyst in the embodiment of this present invention. [Figure 5A]This is an explanatory diagram showing an example of the results of analyzing the X-ray diffraction pattern obtained by powder X-ray diffraction of the metal-supported catalyst in the embodiment of this product. [Figure 5B] This is an explanatory diagram showing another example of the results of analyzing the X-ray diffraction pattern obtained by powder X-ray diffraction of the metal-supported catalyst in the embodiment of this present invention. [Figure 5C] This is an explanatory diagram showing yet another example of the results of analyzing the X-ray diffraction pattern obtained by powder X-ray diffraction of the metal-supported catalyst in the embodiment of this present invention. [Figure 5D] This is an explanatory diagram showing a magnified portion of the X-ray diffraction pattern shown in Figure 5C. [Figure 6A] This is an explanatory diagram showing yet another example of the results of analyzing the X-ray diffraction pattern obtained by powder X-ray diffraction of the metal-supported catalyst in the embodiment of this present invention. [Figure 6B] This is an explanatory diagram showing a magnified portion of the X-ray diffraction pattern shown in Figure 6A. [Figure 7] This is an explanatory diagram showing an example of the results of evaluating the ECSA sweep rate dependence of the metal-supported catalyst in the embodiment of this theory. [Figure 8A] This is an explanatory diagram showing the equivalent circuit. [Figure 8B] This is an explanatory diagram showing the measured values ​​and fitting results of the Nyquist plot obtained for the metal-supported catalyst in the embodiment of this model. [Figure 9A] This diagram illustrates the manufacturing conditions for the metal-supported catalyst and the results of evaluating the characteristics of the fuel cell containing the metal-supported catalyst in an embodiment of this model. [Figure 9B] This is an explanatory diagram showing the results of evaluating the properties of the metal-supported catalyst in the embodiment of this theory. [Modes for carrying out the invention]

[0019] One embodiment of the present invention is described below. However, the present invention is not limited to the examples shown in this embodiment.

[0020] The metal-supported catalyst according to this embodiment (hereinafter referred to as "the catalyst") comprises a carbon support and catalyst metal particles containing a noble metal alloy supported on the carbon support.

[0021] The carbon support contained in this catalyst is a carbon material mainly composed of carbon. The carbon content of the carbon support may be, for example, 70% by weight or more, preferably 75% by weight or more, more preferably 80% by weight or more, and particularly preferably 85% by weight or more.

[0022] Furthermore, the carbon content of the carbon carrier may be, for example, 100% by weight or less, 95% by weight or less, or 90% by weight or less. The carbon content of the carbon carrier may be determined by any combination of the lower limit and the upper limit mentioned above. The carbon content of the carbon carrier is obtained by elemental analysis (combustion method).

[0023] The carbon carrier is preferably a carbonization material. The carbonization material is obtained by carbonizing a raw material containing organic matter. The organic matter content in the carbonization raw material may be, for example, 5% by weight or more and 90% by weight or less, and preferably 10% by weight or more and 80% by weight or less.

[0024] The organic matter contained in the raw materials is not particularly limited as long as it can be carbonized. Even if the organic compound is a polymer (e.g., thermosetting resins and / or thermoplastic resins) It is fine, and / or it may be an organic compound with a smaller molecular weight.

[0025] The carbon support preferably contains nitrogen. That is, the carbon support preferably contains nitrogen atoms in its carbon structure. The nitrogen-containing carbon support is preferably a nitrogen-containing carbonization material. The nitrogen-containing carbonization material can be obtained, for example, by carbonizing a raw material containing nitrogen-containing organic matter. The nitrogen-containing organic matter preferably contains nitrogen-containing organic compounds. The nitrogen-containing organic compound is not particularly limited as long as it is an organic compound that contains nitrogen atoms in its molecule. Furthermore, the nitrogen contained in the carbon support may be introduced by nitrogen doping treatment.

[0026] The nitrogen content of the carbon carrier may be, for example, 0.10% by weight or more, preferably 0.15% by weight or more, more preferably 0.20% by weight or more, even more preferably 0.25% by weight or more, and particularly preferably 0.30% by weight or more. The nitrogen content of the carbon carrier may also be, for example, 10.00% by weight or less. The nitrogen content of the carbon carrier is obtained by elemental analysis (combustion method) of the carbon carrier.

[0027] The carbon carrier is preferably a carbonized material obtained by carbonizing raw materials containing organic matter and metals. In this case, the carbon carrier may be a carbonized material that has undergone a metal removal treatment after carbonization. The metal removal treatment is a treatment that reduces the amount of metal derived from the raw materials contained in the carbonized material. Specifically, the metal removal treatment is preferably, for example, an acidic washing treatment and / or an electrolytic treatment.

[0028] If the carbon carrier is a carbonized material obtained by carbonizing raw materials containing organic matter and metal, the carbon carrier may contain metal derived from the raw materials used in the carbonization (hereinafter referred to as "raw material metal"). In this case, the carbon carrier contains the raw material metal inside the framework that constitutes its porous structure. Even if the carbon carrier is a carbonized material produced through a metal removal treatment as described above, raw material metal remains inside the framework of the carbon carrier. Of the raw material metal contained in the carbon carrier, the weight of the raw material metal contained inside the framework of the carbon carrier may be greater than the weight of the raw material metal contained on the surface of the framework of the carbon carrier.

[0029] The raw metal inside the carbon carrier's framework can be detected, for example, by performing a surface etching treatment on the framework and analyzing the cross-section exposed by the etching treatment. In other words, in this case, if one particle of the carbon carrier is etched, the raw metal can be detected in the cross-section of that particle exposed by the etching treatment. The raw metal contained in the carbon carrier can also be detected, for example, by inductively coupled plasma emission spectroscopy of the carbon carrier.

[0030] The raw material metal content of the carbon carrier (the ratio of the weight of the raw material metal contained in the carbon carrier to the weight of the carbon carrier) may be, for example, 0.001% by weight or more, 0.005% by weight or more, 0.01% by weight or more, or 0.02% by weight or more. Furthermore, the raw material metal content of the carbon carrier may be, for example, 5% by weight or less, 4% by weight or less, 3% by weight or less, 2% by weight or less, 1% by weight or less, 0.8% by weight or less, or 0.5% by weight or less. The raw material metal content of the carbon carrier may be determined by any combination of the lower limit and the upper limit mentioned above. The raw material metal content of the carbon carrier can be obtained, for example, by inductively coupled plasma emission spectroscopy of the carbon carrier.

[0031] The raw material metal is preferably a transition metal. Specifically, the raw material metal is preferably a transition metal belonging to groups 3 to 12 of the periodic table, and is particularly preferably a transition metal belonging to the fourth period of groups 3 to 12 of the periodic table.

[0032] The raw material metal may be a transition metal other than platinum. Furthermore, the raw material metal may be a transition metal other than noble metals (e.g., ruthenium (Ru), palladium (Pd), rhodium (Rh), silver (Ag), osmium (Os), iridium (Ir), platinum (Pt), and gold (Au)).

[0033] Specifically, the raw material metal may be one or more selected from the group consisting of scandium (Sc), titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), yttrium (Y), zirconium (Zr), niobium (Nb), molybdenum (Mo), ruthenium (Ru), rhodium (Rh), palladium (Pd), silver (Ag), lanthanides (e.g., gadolinium (Gd)), and actinides. Preferably, it is one or more selected from the group consisting of Fe, Co, Ni, Cu, and Zn. More preferably, it is one or more selected from the group consisting of Fe, Co, Ni, and Zn. Particularly preferably, it is one or more selected from the group consisting of Co, Ni, and Zn.

[0034] Carbonization in the production of carbonized materials is carried out by heating the raw material to a temperature at which the organic matter contained in the raw material is carbonized. The carbonization temperature is not particularly limited as long as it is the temperature at which the raw material is carbonized, but for example, it is preferably 1200°C or higher, more preferably 1300°C or higher, even more preferably 1400°C or higher, and particularly preferably 1500°C or higher.

[0035] Furthermore, the carbonization temperature may be, for example, 3000°C or lower, preferably 2500°C or lower, and particularly preferably 2000°C or lower. The carbonization temperature may be determined by any combination of the lower limit and the upper limit mentioned above. The heating rate to the carbonization temperature is not particularly limited and may be, for example, 0.5°C / min or more and 300°C / min or less. Carbonization is preferably carried out in an inert atmosphere such as a nitrogen atmosphere.

[0036] Carbonization may be carried out under normal pressure (atmospheric pressure), but it is preferable to carry it out under pressurized pressure (at a pressure greater than atmospheric pressure). When carbonization is carried out under pressurized pressure, the pressure of the atmosphere in which carbonization is carried out may be, for example, 0.05 MPa or higher in gauge pressure, preferably 0.15 MPa or higher, more preferably 0.20 MPa or higher, even more preferably 0.40 MPa or higher, and particularly preferably 0.50 MPa or higher. There is no particular upper limit to the pressure of the atmosphere in which carbonization is carried out, but the pressure may be, for example, 10 MPa or less in gauge pressure.

[0037] The carbon carrier is preferably a carbonized material that has been subjected to graphitization treatment after carbonization. That is, the carbon carrier is preferably a carbonized material obtained by, for example, subjecting a carbonized material obtained by carbonizing a raw material containing organic matter to graphitization treatment.

[0038] The graphitization treatment is carried out by heating the carbonization material at a temperature at which graphitization progresses. The heating temperature for heating the carbonization material in the graphitization treatment is not particularly limited as long as it is a temperature at which graphitization progresses in the carbonization material, but it is preferable that it is a higher temperature than the carbonization temperature required to obtain the carbonization material.

[0039] Specifically, the heating temperature in the graphitization treatment may be, for example, 1300°C or higher, preferably 1400°C or higher, more preferably 1500°C or higher, even more preferably 1600°C or higher, even more preferably 1700°C or higher, even more preferably 1750°C or higher, and particularly preferably 1800°C or higher.

[0040] Furthermore, the heating temperature in the graphitization treatment may be, for example, 3000°C or less, preferably 2500°C or less, more preferably 2400°C or less, even more preferably 2300°C or less, even more preferably 2250°C or less, even more preferably 2200°C or less, even more preferably 2150°C or less, and particularly preferably 2100°C or less. The heating temperature in the graphitization treatment may be determined by arbitrarily combining any of the lower limits and any of the upper limits mentioned above. The rate of heating up to the heating temperature in the graphitization treatment is not particularly limited and may be, for example, 0.5°C / min or more and 300°C / min or less. The graphitization treatment is preferably carried out in an inert atmosphere such as a nitrogen atmosphere.

[0041] When the carbon carrier is a carbonized material that has been subjected to graphitization treatment after carbonization, it is preferable not to subject the carbonized material after graphitization treatment to pulverization treatment. That is, in the production of the carbon carrier, for example, it is preferable to adjust the median diameter by subjecting the carbonized material obtained by carbonization of the raw material to pulverization treatment, and then subject the pulverized carbonized material to graphitization treatment, and not subject the carbonized material after graphitization treatment to pulverization treatment.

[0042] The carbon support is preferably a carbon material that exhibits catalytic activity. In other words, in this case, the carbon support is a carbon catalyst that exhibits catalytic activity on its own. The carbon support, which is a carbon catalyst, is preferably a carbonized material obtained by carbonizing a raw material containing organic matter and metal, as described above.

[0043] The catalytic activity exhibited by the carbon support is preferably, for example, reducing activity and / or oxidizing activity, more preferably oxygen reducing activity and / or hydrogen oxidizing activity, and particularly preferably at least oxygen reducing activity.

[0044] In this catalyst, the catalyst metal particles supported on the carbon support include a noble metal alloy. A noble metal alloy is an alloy of a noble metal and a metal other than a noble metal (hereinafter referred to as "non-noble metal"). That is, a noble metal alloy includes one or more noble metals and one or more non-noble metals. The catalyst metal particles may further include noble metals that do not form an alloy (hereinafter sometimes referred to as "pure noble metal").

[0045] The precious metal is preferably one or more selected from the group consisting of ruthenium (Ru), palladium (Pd), rhodium (Rh), silver (Ag), osmium (Os), iridium (Ir), platinum (Pt), and gold (Au), more preferably one or more selected from the group consisting of Ru, Pd, Rh, Ir, and Pt, and particularly preferably Pt.

[0046] In other words, the catalyst metal particles preferably contain a platinum alloy. A platinum alloy is an alloy of platinum and a non-precious metal. That is, a platinum alloy contains platinum and one or more non-precious metals. The platinum alloy may also contain one or more other precious metals, or it may not contain any other precious metals. Furthermore, the catalyst metal particles may also contain platinum that does not form an alloy (hereinafter sometimes referred to as "pure platinum").

[0047] The non-precious metals constituting the precious metal alloy are not particularly limited as long as they are metals other than precious metals that form an alloy with the precious metal, but are preferably transition metals other than precious metals. Specifically, the non-precious metals included in the precious metal alloy are preferably one or more selected from the group consisting of titanium (Ti), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), niobium (Nb), and cerium (Ce), more preferably one or more selected from the group consisting of Fe, Co, and Ni, and particularly preferably one or more selected from the group consisting of Co and Ni.

[0048] When the carbon support is a carbonized material of a raw material containing an organic substance and a raw material metal, the catalytic metal particles supported on the carbon support may contain the same kind of metal as the raw material metal, or may not contain the same kind of metal as the raw material metal.

[0049] The catalytic activity of the catalytic metal particles is not particularly limited as long as the effects of the present invention can be obtained. However, the catalytic metal particles preferably exhibit, for example, reduction activity and / or oxidation activity, more preferably oxygen reduction activity and / or hydrogen oxidation activity, and particularly preferably exhibit at least oxygen reduction activity.

[0050] This catalyst has, in the Raman spectrum obtained by Raman spectroscopy, the intensity of the 2D band having a peak top in the vicinity of a Raman shift of 2680 cm -1 (Specifically, for example, in the range of 1550 cm -1 or more and 1700 cm -1 or less) with respect to the intensity of the G band having a peak top in the vicinity of a Raman shift of 1600 cm -1 (Specifically, for example, in the range of 2600 cm -1 or more and 2800 cm -1 or less). (Hereinafter referred to as the "Raman 2D / G ratio"). It preferably has a carbon structure showing a ratio of 0.20 or more and 1.00 or less.

[0051] The Raman 2D / G ratio of this catalyst is, for example, more preferably 0.25 or more, further preferably 0.30 or more, still further preferably 0.35 or more, still further preferably 0.40 or more, still further preferably 0.45 or more, still further preferably 0.50 or more, and particularly preferably 0.55 or more.

[0052] Furthermore, the Raman 2D / G ratio of this catalyst is preferably 0.95 or less, more preferably 0.90 or less, even more preferably 0.85 or less, even more preferably 0.80 or less, even more preferably 0.75 or less, even more preferably 0.70 or less, even more preferably 0.65 or less, and particularly preferably 0.60 or less. The Raman 2D / G ratio of this catalyst may be determined by any combination of the lower limit and the upper limit mentioned above.

[0053] Here, the Raman 2D / G ratio of a carbon material indicates the number of layers constituting the graphene laminate contained in the carbon structure of that carbon material. That is, if the intensity of the 2D band is greater than the intensity of the G band (Raman 2D / G ratio > 1), then there is a single layer of graphene. If the intensity of the 2D band is the same as the intensity of the G band (Raman 2D / G ratio = 1), then there are approximately two layers of graphene laminate. If the intensity of the 2D band is less than the intensity of the G band (Raman 2D / G ratio < 1), then there are three or more layers of graphene laminate. The specific number of layers can be determined from the ratio of the intensity of the 2D band (peak top height) to the intensity of the G band (peak top height).

[0054] Carbon structures exhibiting a Raman 2D / G ratio that is too low, i.e., carbon structures with too many layers in the graphene stack, have poor durability because the relative amount of the edge portion relative to the basal surface, which is the starting point for oxidative degradation, is too large. In contrast, carbon structures exhibiting a Raman 2D / G ratio above the lower limit mentioned above include few-layer graphene (Few Layer Graphene) in which the number of layers in the graphene stack is controlled to an appropriate range (for example, around 2 to 3 layers), and the relative amount of the edge portion relative to the exposed basal surface is controlled to an appropriate range, thus contributing to improved durability.

[0055] On the other hand, the edge portions also function as support sites for catalyst metal particles. Therefore, carbon structures exhibiting an excessively large Raman 2D / G ratio have insufficient relative amounts of edge portions to the basal surface, making them unsuitable for supporting catalyst metal particles. In contrast, carbon structures exhibiting a Raman 2D / G ratio below the aforementioned upper limit contain an appropriate amount of edge portions relative to the basal surface, resulting in excellent suitability for supporting catalyst metal particles and, consequently, contributing to improved durability and / or catalytic function of the metal-supported catalyst.

[0056] This catalyst exhibits a Raman shift of 1340 cm⁻¹ in the Raman spectrum obtained by Raman spectroscopy. -1 Nearby (specifically, for example, 1320cm) -1 Above, 1360cm -1 The half-width at half maximum (hereinafter referred to as "Raman D half-width at half maximum") of the D-band with a peak top within the following range is 41.0 cm. -1 It is preferable to have the following carbon structure.

[0057] The Raman D half-width of this catalyst is, for example, 40.0 cm². -1 It is more preferable that the following be the case: 38.0 cm -1 It is even more preferable that the following conditions apply: 36.0 cm -1 It is even more preferable that the following conditions apply: 34.0 cm -1 It is even more preferable that the following conditions apply: 32.0 cm -1 It is even more preferable that the following conditions apply: 30.0 cm -1 It is even more preferable that the following conditions apply: 28.0 cm -1 It is even more preferable that the following conditions apply: 27.0 cm -1 It is even more preferable that the following conditions apply: 26.5 cm -1 It is even more preferable that the following conditions apply: 26.0 cm -1 The following is particularly preferable:

[0058] Furthermore, the Raman D half-width of this catalyst is, for example, 20.0 cm. -1 It may be greater than or equal to 21.0 cm. -1 Preferably, it should be 22.0 cm or more. -1It is more preferable that the length be greater than or equal to 22.5 cm. -1 It is even more preferable that the length be greater than or equal to 23.0 cm. -1 It is even more preferable that the length be greater than or equal to 23.5 cm. -1 It is even more preferable that the length be greater than or equal to 24.0 cm. -1 It is even more preferable that the length be greater than or equal to 24.5 cm. -1 The above is particularly preferable. The Raman D half-width of this catalyst may be determined by any combination of the lower limit and the upper limit mentioned above.

[0059] According to the reference (A. Sadezky et al., Carbon 43 (2005) 1731-1742), in the Raman spectrum of carbon materials, the D band represents components derived from carbon atoms close to disordered lattices, such as the edges of graphene layers. The half-width at half maximum (FMAX) of the D band indicates the crystallinity of carbon around the edges. That is, as the crystallinity of carbon around the edges in a carbon structure increases, the Raman D FMAX of that carbon structure decreases. Therefore, carbon structures exhibiting a Raman D FMAX below the upper limit mentioned above contain highly crystalline carbon around the edges, thus contributing to improved durability.

[0060] On the other hand, carbon structures exhibiting a Raman D half-width that is too small have excessively high crystallinity of carbon around the edges, making them unsuitable for supporting catalyst metal particles. In contrast, carbon structures exhibiting a Raman D half-width above the lower limit mentioned above contain carbon with appropriate crystallinity around the edges, resulting in excellent suitability for supporting catalyst metal particles and, consequently, contributing to improved durability and / or catalytic function of the metal-supported catalyst.

[0061] This catalyst has a BET specific surface area of ​​350 (m²). 2 It is preferable that the value is 1 / g-carbon support or higher. In this specification, the numerical unit " / g-carbon support" indicates the value per gram of carbon support contained in this catalyst. On the other hand, the numerical unit " / g" indicates the value per gram of this catalyst.

[0062] The BET specific surface area of ​​this catalyst is, for example, 400 (m²). 2 It is more preferable that the amount is 450 (m²) or more (1 / g-carbon support), and more preferably 450 (m²). 2 It is even more preferable that the amount is 500 (m²) or more (1 / g-carbon support), and 500 (m²) 2 It is more preferably 550 (m²) or more (g² - carbon support), 2 It is more preferably 600 (m²) or more (g² - carbon support), 2 It is more preferably 650(m²) or more (g² - carbon support), 2 It is more preferably 700 (m²) or more (g² - carbon support), and 2 It is more preferably 750(m²) or more (1 / g-carbon support), 2 It is even more preferable that the value be 800 (m²) or more (1 / g-carbon support), and 800 (m²). 2 It is even more preferable that the amount is 850 (m²) or more (1 / g-carbon support), and 2 It is even more preferable that the value be 900 (m²) or more (1 / g-carbon support). 2 It is even more preferable that the carbon support ( / g) is 950(m 2 It is particularly preferable that the BET specific surface area of ​​this catalyst is 3000 (m²). 2 / g-carbon support) may be less than or equal to 2500(m 2 / g-carbon support) may be less than or equal to 2000(m 2 / g-carbon support) may be less than or equal to 1800(m 2 / g-carbon support) may be less than 1600(m 2 / g-carbon support) may be less than or equal to 1400(m 2 The BET specific surface area of ​​this catalyst may be less than or equal to ( / g-carbon support). The BET specific surface area of ​​this catalyst may be determined by any combination of the lower limit and the upper limit mentioned above.

[0063] The BET specific surface area (m²) of this catalyst 2 The BET specific surface area (m²) of this catalyst is obtained by the BET method from the nitrogen adsorption isotherm at a temperature of 77K (g-carbon support). 2 It is calculated from the weight ratio of carbon supports contained in the catalyst obtained by inductively coupled plasma atomic emission spectroscopy ( / g) and the weight ratio of carbon supports contained in the catalyst obtained by inductively coupled plasma atomic emission spectroscopy.

[0064] The catalyst preferably has an average pore diameter of 8.0 nm or less. The average pore diameter of the catalyst is more preferably 7.0 nm or less, even more preferably 6.0 nm or less, even more preferably 5.0 nm or less, even more preferably 4.5 nm or less, even more preferably 4.0 nm or less, even more preferably 3.5 nm or less, and even more preferably 3.0 nm or less. The average pore diameter of the catalyst may also be, for example, 1.0 nm or more, preferably 1.5 nm or more, and particularly preferably 2.0 nm or more. The average pore diameter of the catalyst may be determined by any combination of the lower limit and the upper limit mentioned above. The average pore diameter of the catalyst is obtained from the nitrogen adsorption isotherm at a temperature of 77 K by the BJH method.

[0065] If the average pore size of a metal-supported catalyst is too large, for example, when the metal-supported catalyst is used as an electrode catalyst in a fuel cell, ionomers can easily enter the pores of the metal-supported catalyst. As a result, the catalyst metal particles supported in the pores become coated with ionomers, which can easily lead to a decrease in catalytic activity. In contrast, a porous structure with an average pore size below the upper limit mentioned above makes it difficult for ionomers to enter the pores, thus contributing to improved durability and / or catalytic function.

[0066] Furthermore, if the average pore size of the metal-supported catalyst is too small, the catalyst metal particles are more likely to be supported on the outer surface of the carbon support than within the pores, resulting in lower durability. In contrast, a porous structure with an average pore size above the lower limit mentioned above allows the catalyst metal particles to be effectively supported within the pores, thus contributing to improved durability.

[0067] The catalyst preferably has a ratio of the weight of the precious metal contained in the catalyst (more specifically, the weight of the precious metal contained in the catalyst metal particles) to the weight of the catalyst (hereinafter referred to as "precious metal content") of 35% by weight or more. The precious metal content of the catalyst is more preferably 37% by weight or more, even more preferably 40% by weight or more, even more preferably 42% by weight or more, even more preferably 45% by weight or more, and particularly preferably 47% by weight or more. The precious metal content of the catalyst may also be, for example, 90% by weight or less, 80% by weight or less, 70% by weight or less, or 60% by weight or less. The precious metal content of the catalyst may be determined by any combination of the lower limit and the upper limit mentioned above. The precious metal content of the catalyst is obtained by inductively coupled plasma atomic emission spectroscopy.

[0068] The catalyst preferably has a molar ratio of noble metals to non-noble metals contained in it (hereinafter referred to as the "noble metal / non-noble metal molar ratio") of 1.0 or higher. The noble metal / non-noble metal molar ratio of the catalyst is more preferably 1.5 or higher, even more preferably 2.0 or higher, still more preferably 2.5 or higher, and particularly preferably 3.0 or higher.

[0069] Furthermore, the noble metal / non-noble metal molar ratio of this catalyst may be, for example, 20.0 or less, preferably 15.0 or less, more preferably 14.0 or less, even more preferably 13.0 or less, even more preferably 12.0 or less, even more preferably 11.0 or less, and particularly preferably 10.5 or less. The noble metal / non-noble metal molar ratio of this catalyst may be determined by any combination of the lower limit and the upper limit mentioned above. The noble metal / non-noble metal molar ratio of this catalyst is calculated from the respective mole fractions of the noble metal and non-noble metal contained in the catalyst, obtained by inductively coupled plasma atomic emission spectroscopy.

[0070] The catalyst preferably has an alloy composition heterogeneity of 0.55 or less, calculated by the following formula (I). JPEG2023129139000004.jpg11170

[0071] In equation (I) above, the theoretical lattice constant and the experimentally measured lattice constant are the theoretical and experimentally measured lattice constants of the noble metal alloy contained in the catalyst, respectively. The theoretical lattice constant of the noble metal alloy contained in the catalyst is calculated using the mole fractions of the noble metal and non-noble metal obtained by inductively coupled plasma emission spectroscopy of the catalyst. The experimentally measured lattice constant of the noble metal alloy contained in the catalyst is calculated using the position of the peak top (diffraction angle 2θ) of the diffraction peak corresponding to the (111) plane of the noble metal alloy in the X-ray diffraction pattern obtained by powder X-ray diffraction of the catalyst. Note that if the noble metal alloy contained in the catalyst is a platinum alloy, the position of the peak top of the diffraction peak corresponding to the (111) plane of the platinum alloy in the X-ray diffraction pattern of the catalyst will be within the range of diffraction angle 2θ from 35° to 44°.

[0072] The alloy composition heterogeneity of this catalyst is more preferably 0.50 or less, even more preferably 0.48 or less, even more preferably 0.45 or less, even more preferably 0.42 or less, even more preferably 0.40 or less, and particularly preferably 0.38 or less. Furthermore, the alloy composition heterogeneity of this catalyst may be, for example, 0.01 or more, or 0.05 or more. The alloy composition heterogeneity of this catalyst may be specified by any combination of the lower limit and the upper limit mentioned above. An alloy composition heterogeneity below the upper limit indicates high uniformity in the composition of the noble metal alloy contained in the metal-supported catalyst, contributing to improved durability and / or catalytic function.

[0073] It is preferable that the catalyst has a half-value asymmetry and quarter-value asymmetry calculated by formulas (II) and (III) below, respectively, of 0.55 or less. JPEG2023129139000005.jpg11170JPEG2023129139000006.jpg10170

[0074] In equations (II) and (III) above, D m D is the value of the diffraction angle 2θ in which the diffraction line shows maximum intensity in the range of diffraction angle 2θ in which the diffraction peak of the (111) plane of the noble metal alloy appears in the X-ray diffraction pattern obtained by powder X-ray diffraction of this catalyst (for example, if the noble metal alloy is a platinum alloy, the diffraction angle 2θ range in which the diffraction peak of the (111) plane of the platinum alloy appears, where the diffraction line shows maximum intensity). Lh D is the smallest diffraction angle 2θ value among the diffraction angles 2θ in which the diffraction line exhibits half the intensity of the maximum intensity within that range. Hh D is the value of the largest diffraction angle 2θ among the diffraction angles 2θ in which the diffraction line exhibits half the intensity of the maximum intensity within that range. Lq D is the smallest diffraction angle 2θ value among the diffraction angles 2θ in which the diffraction line exhibits an intensity of one-quarter of the maximum intensity within that range. Hq This is the largest diffraction angle 2θ value among those within the range where the diffraction line exhibits an intensity of one-quarter of its maximum intensity.

[0075] The half-value asymmetry and quarter-value asymmetry of this catalyst are more preferably 0.53 or less, even more preferably 0.50 or less, even more preferably 0.48 or less, even more preferably 0.45 or less, and particularly preferably 0.43 or less. Furthermore, the half-value asymmetry and quarter-value asymmetry of this catalyst may also be 0.01 or greater, or 0.05 or greater. The half-value asymmetry and quarter-value asymmetry of this catalyst may each be determined by arbitrarily combining any of the lower and upper limits mentioned above. Half-value asymmetry and quarter-value asymmetry below the upper limits mentioned above indicate high uniformity in the composition of the noble metal alloy contained in the metal-supported catalyst, contributing to improved durability and / or catalytic function.

[0076] The number-average particle diameter of the catalyst metal particles contained in this catalyst is preferably 8.0 nm or less. The number-average particle diameter of the catalyst metal particles is preferably, for example, 7.5 nm or less, more preferably 7.0 nm or less, even more preferably 6.5 nm or less, even more preferably 6.0 nm or less, even more preferably 5.5 nm or less, even more preferably 5.0 nm or less, even more preferably 4.5 nm or less, even more preferably 4.0 nm or less, and particularly preferably 3.5 nm or less. The number-average particle diameter of the catalyst metal particles may also be, for example, 1.0 nm or more, 1.5 nm or more, or 2.0 nm or more. The number-average particle diameter of the catalyst metal particles contained in this catalyst may be determined by any combination of the lower limit and the upper limit mentioned above. The number-average particle diameter of the catalyst metal particles contained in this catalyst is obtained by powder X-ray diffraction of this catalyst. Catalyst metal particles having a number-average particle diameter below the upper limit mentioned above contribute to improved durability and / or catalytic function. If the number-average particle size of the catalyst metal particles is too large, the metal surface area per unit metal mass of the catalyst metal particles will be too small, which can lead to a deterioration in output characteristics. Conversely, a number-average particle size below the upper limit mentioned above increases the metal surface area per unit metal mass of the catalyst metal particles, contributing to an improvement in output characteristics.

[0077] The volume-average particle diameter of the catalyst metal particles contained in this catalyst is preferably 8.0 nm or less. The volume-average particle diameter of the catalyst metal particles is preferably, for example, 7.5 nm or less, more preferably 7.0 nm or less, even more preferably 6.5 nm or less, even more preferably 6.0 nm or less, even more preferably 5.5 nm or less, even more preferably 5.0 nm or less, even more preferably 4.5 nm or less, and particularly preferably 4.2 nm or less. The volume-average particle diameter of the catalyst metal particles may also be, for example, 1.0 nm or more, 1.5 nm or more, or 2.0 nm or more. The volume-average particle diameter of the catalyst metal particles contained in this catalyst may be determined by any combination of the lower limit and the upper limit mentioned above. The volume-average particle diameter of the catalyst metal particles contained in this catalyst is obtained by powder X-ray diffraction of this catalyst. If the volume-average particle size of the catalyst metal particles is too large, the metal surface area per unit mass of metal will be too small, which may lead to a deterioration in output characteristics. Furthermore, large variations in particle size can make the metal constituting the surface of the catalyst metal particles more susceptible to dissolution as metal ions. In contrast, a volume-average particle size below the upper limit mentioned above increases the metal surface area per unit mass of metal of the catalyst metal particles, contributing to improved output characteristics, as well as suppressing the dissolution of the catalyst metal particles, thereby contributing to improved durability and / or catalytic function.

[0078] Preferably, the catalyst has a sweep rate dependence of the electrochemical effective specific surface area (ECSA) of the noble metal contained in the catalyst (hereinafter referred to as "ECSA sweep rate dependence") of 60% or more, calculated by the following formula (IV). JPEG2023129139000007.jpg17170

[0079] The numerical unit " / g-precious metal" indicates the value per gram of precious metal contained in this catalyst. For example, the numerical unit " / g-Pt" indicates the value per gram of platinum contained in this catalyst.

[0080] In the above formula (IV), "ECSA@1000mV" and "ECSA@10mV" are the ECSA (m³) per gram of noble metal contained in the catalyst, obtained by cyclic voltammetry with a sweep rate of 1000mV / sec and cyclic voltammetry with a sweep rate of 10mV / sec, respectively, using a rotating ring disk electrode device having a working electrode on which the catalyst is supported. 2 / g - precious metals) (that is, "ECSA@1000mV(m 2 / g-precious metal)” and “ECSA@10mV(m 2 It is a precious metal (g).

[0081] The ECSA sweep rate dependence of this catalyst is more preferably 65% ​​or more, even more preferably 70% or more, even more preferably 75% or more, and particularly preferably 80% or more. Furthermore, the ECSA sweep rate dependence of this catalyst may be less than 100%, 95% or less, or 90% or less. The ECSA sweep rate dependence of this catalyst may be determined by any combination of the lower limit and upper limit mentioned above.

[0082] For example, if the catalyst metal particles supported on the carbon support in this catalyst include platinum as a precious metal, the sweep rate dependence (%) of the ECSA of the platinum contained in this catalyst is expressed in formula (IV) above as "ECSA@1000mV" and "ECSA@10mV", respectively, by cyclic voltammetry with a sweep rate of 1000mV / sec and cyclic voltammetry with a sweep rate of 10mV / sec using a rotating ring disk electrode device having a working electrode on which the catalyst is supported, and by cyclic voltammetry with a sweep rate of 10mV / sec. 2 / g-Pt)(that is, "ECSA@1000mV(m 2 / g‐Pt)” and “ECSA@10mV(m 2 It is calculated using ( / g - Pt)

[0083] Catalyst metal particles supported inside the pores of a carbon support are less prone to aggregation than catalyst metal particles supported on the outer surface of the carbon support, thus contributing to catalytic activity and / or durability. In this regard, in a metal-supported catalyst, when a large proportion of catalyst metal particles are supported on the outer surface of the carbon support, the decrease in ECSA with increasing potential sweep rate in the cyclic voltammetry described above is small. On the other hand, in a metal-supported catalyst, when a large proportion of catalyst metal particles are supported inside the pores of the carbon support, the decrease in ECSA with increasing potential sweep rate in the cyclic voltammetry described above is large. Therefore, the magnitude of the ECSA sweep rate dependence of a metal-supported catalyst reflects the relative amount of catalyst metal particles supported inside the pores of the carbon support to the catalyst metal particles supported on the outer surface of the carbon support.

[0084] The method for producing a metal-supported catalyst according to this embodiment (hereinafter referred to as "this method") is a method for producing a metal-supported catalyst comprising a carbon carrier and catalyst metal particles containing a noble metal alloy supported on the carbon carrier, and preferably includes: a first impregnation step of impregnating the carbon carrier with a precursor of one of the noble metals and non-noble metals constituting the noble metal alloy (hereinafter referred to as "first metal"); a first gas-phase reduction step of subjecting the carbon carrier impregnated with the precursor of the first metal to a gas-phase reduction treatment to obtain a first metal-supported catalyst supporting the first metal; a second impregnation step of impregnating the first metal-supported catalyst with a precursor of the other of the noble metal and non-noble metals (hereinafter referred to as "second metal"); and a second gas-phase reduction step of subjecting the first metal-supported catalyst impregnated with the precursor of the second metal to a gas-phase reduction treatment, and then to an alloying treatment to obtain a metal-supported catalyst on which catalyst metal particles containing an alloy of the first metal and the second metal are supported.

[0085] In the first impregnation step, a precursor of the first metal is impregnated into a carbon support that has not yet been impregnated with any precursors of either the noble metal or the non-noble metal that should constitute the noble metal alloy contained in the catalyst metal particles. The first metal may be either the noble metal or the non-noble metal that should constitute the noble metal alloy contained in the catalyst metal particles, but if a non-noble metal with a high ionization tendency is selected as the first metal, the non-noble metal, which is the first metal, will be ionized when the noble metal, which is the second metal, is impregnated in the second impregnation step. Therefore, it is preferable to select a noble metal with a lower ionization tendency.

[0086] In this method, when forming a noble metal alloy containing two or more noble metals and / or two or more non-noble metals, in the first impregnation step, as a precursor of the first metal, only one noble metal precursor or only one non-noble metal precursor may be impregnated into the carbon carrier, or two or more noble metal precursors or two or more non-noble metal precursors may be impregnated into the carbon carrier. Furthermore, when impregnating the carbon carrier with two or more precursors of the first metal, the first impregnation step may, for example, first impregnate the carbon carrier with one of the two or more precursors of the first metal, and then impregnate the carbon carrier with the other precursor of the first metal, or it may include simultaneously impregnating the carbon carrier with two or more precursors of the first metal.

[0087] The method for impregnating the carbon carrier with a precursor of a primary metal is not particularly limited as long as the effects of the present invention are obtained, but it is preferable, for example, to impregnate the carbon carrier with a solution containing the precursor of the primary metal. Here, when impregnating the carbon carrier with two or more precursors of primary metals, the first impregnation step may include, for example, first impregnating the carbon carrier with a solution containing one of the two or more precursors of primary metals, and then impregnating the carbon carrier with a solution containing the other precursor of primary metals, or impregnating the carbon carrier with a solution containing two or more precursors of primary metals.

[0088] The atmospheric pressure (atmospheric pressure) in which the first impregnation step is carried out is not particularly limited as long as the effects of the present invention are obtained, and may be normal pressure (atmospheric pressure). However, the first impregnation step preferably includes, for example, holding a solution containing a precursor of the first metal and a carbon support under reduced pressure. By holding the solution containing the precursor of the first metal and a carbon support under reduced pressure, the inside of the pores of the carbon support is effectively degassed, and the precursor is effectively impregnated into the inside of the pores.

[0089] The pressure of the reduced-pressure atmosphere holding the solution containing the primary metal precursor and carbon support is not particularly limited as long as the effects of the present invention are obtained, but for example, it may be -0.02 MPa (minus 0.02 MPa) or less in gauge pressure, preferably -0.04 MPa or less, more preferably -0.06 MPa or less, even more preferably -0.08 MPa or less, and particularly preferably -0.10 MPa or less. Alternatively, the pressure of the reduced-pressure atmosphere holding the solution containing the primary metal precursor and carbon support may be, for example, -0.1013 MPa or more in gauge pressure. The pressure of the reduced-pressure atmosphere holding the solution containing the primary metal precursor and carbon support may be specified by any combination of the lower limit and the upper limit mentioned above.

[0090] In the first impregnation step, the time for holding the solution containing the precursor of the first metal and the carbon support under reduced pressure is not particularly limited as long as the effects of the present invention are obtained, but for example it may be 10 minutes or more, preferably 20 minutes or more, more preferably 30 minutes or more, even more preferably 40 minutes or more, even more preferably 50 minutes or more, and particularly preferably 55 minutes or more. Also, the time for holding the solution containing the precursor of the first metal and the carbon support under reduced pressure may be, for example, 24 hours or less, 5 hours or less, or 3 hours or less. The time for holding the solution containing the precursor of the first metal and the carbon support under reduced pressure may be determined by any combination of the lower limit and the upper limit mentioned above.

[0091] Furthermore, the first impregnation step preferably includes holding a solution containing the precursor of the first metal and the carbon support under pressure. By holding the solution containing the precursor of the first metal and the carbon support under pressure, the precursor is effectively impregnated into the pores of the carbon support.

[0092] The pressure of the pressurized atmosphere holding the solution containing the primary metal precursor and carbon support is not particularly limited as long as the effects of the present invention are obtained, but for example, it may be 0.03 MPa or higher in gauge pressure, preferably 0.06 MPa or higher, more preferably 0.09 MPa or higher, even more preferably 0.12 MPa or higher, and particularly preferably 0.15 MPa or higher. Alternatively, the pressure of the pressurized atmosphere holding the solution containing the primary metal precursor and carbon support may be 10 MPa or less in gauge pressure, or 5 MPa or less. The pressure of the pressurized atmosphere holding the solution containing the primary metal precursor and carbon support may be determined by any combination of the lower limit and the upper limit mentioned above.

[0093] In the first impregnation step, the time for holding the solution containing the precursor of the first metal and the carbon support under pressure is not particularly limited as long as the effects of the present invention are obtained, but for example it may be 10 minutes or more, preferably 20 minutes or more, more preferably 30 minutes or more, even more preferably 40 minutes or more, even more preferably 50 minutes or more, and particularly preferably 55 minutes or more. Also, the time for holding the solution containing the precursor of the first metal and the carbon support under pressure may be, for example, 24 hours or less, 5 hours or less, or 3 hours or less. The time for holding the solution containing the precursor of the first metal and the carbon support under pressure may be determined by any combination of the lower limit and the upper limit mentioned above.

[0094] The first impregnation step preferably involves first holding the solution containing the precursor of the first metal and the carbon support under reduced pressure, and then holding it under pressure. In this case, the precursor of the first metal is impregnated very effectively into the pores of the carbon support.

[0095] The first impregnation step preferably includes stirring the solution containing the precursor of the first metal and the carbon support before holding the solution under reduced pressure and / or before holding the solution under pressure. By stirring the solution containing the precursor of the first metal and the carbon support before holding under reduced pressure and / or before holding under pressure, the precursor is effectively impregnated into the pores of the carbon support.

[0096] Furthermore, the first impregnation step preferably includes holding the solution containing the precursor of the first metal and the carbon support under reduced pressure, and / or holding the solution containing the precursor of the first metal and the carbon support under pressure, and then mixing the solution containing the precursor of the first metal and the carbon support while stirring. By mixing the solution containing the precursor of the first metal and the carbon support while stirring after holding under reduced pressure and / or after holding under pressure, the precursor is effectively impregnated into the pores of the carbon support.

[0097] The time for stirring the solution containing the primary metal precursor and the carbon support is not particularly limited as long as the effects of the present invention are obtained, but for example it may be 0.1 hours or more, preferably 0.5 hours or more, more preferably 1 hour or more, even more preferably 5 hours or more, even more preferably 10 hours or more, even more preferably 18 hours or more, even more preferably 24 hours or more, even more preferably 35 hours or more, even more preferably 50 hours or more, and especially preferably 65 hours or more. Furthermore, this stirring and mixing time may be, for example, 120 hours or less, 96 hours or less, or 72 hours or less. The time for stirring the solution containing the primary metal precursor and the carbon support may be determined by any combination of the lower limit and the upper limit mentioned above.

[0098] The ambient temperature (air temperature) in which the first impregnation step is carried out is not particularly limited as long as the effects of the present invention are obtained, and may be room temperature (for example, about 25°C). However, it is preferable that the first impregnation step includes, for example, maintaining a solution containing a precursor of the first metal and a carbon support at a low temperature. By maintaining a solution containing a precursor of the first metal and a carbon support at a low temperature, adsorption is promoted by equilibrium shift and / or dissolution of gas molecules is promoted, so that the precursor is effectively impregnated into the pores of the carbon support.

[0099] In other words, the first impregnation step preferably includes holding the solution containing the precursor of the first metal and the carbon support under reduced pressure and at a low temperature. Alternatively, the first impregnation step preferably includes holding the solution containing the precursor of the first metal and the carbon support under pressure and at a low temperature. Alternatively, the first impregnation step preferably includes mixing the solution containing the precursor of the first metal and the carbon support with stirring at a low temperature before holding the solution containing the precursor of the first metal and the carbon support under reduced pressure and / or before holding the solution containing the precursor of the first metal and the carbon support under pressure. Alternatively, the first impregnation step preferably includes mixing the solution containing the precursor of the first metal and the carbon support with stirring at a low temperature after holding the solution containing the precursor of the first metal and the carbon support under reduced pressure and / or after holding the solution containing the precursor of the first metal and the carbon support under pressure.

[0100] In the first impregnation step, the low temperature at which the solution containing the precursor of the first metal and the carbon support is held is not particularly limited as long as the effects of the present invention are obtained, but is preferably 20°C or lower, more preferably 15°C or lower, even more preferably 10°C or lower, and particularly preferably 5°C or lower. Furthermore, the low temperature at which the solution containing the precursor of the first metal and the carbon support is held may be, for example, above 0°C or above 1°C. The low temperature at which the solution containing the precursor of the first metal and the carbon support is held may be determined by arbitrarily combining any of the lower limits and any of the upper limits mentioned above.

[0101] In the first gas-phase reduction step, the carbon support impregnated with the precursor of the first metal in the first impregnation step is subjected to a gas-phase reduction treatment (hereinafter referred to as the "first gas-phase reduction treatment") to obtain a first metal-supported catalyst containing the carbon support and the first metal supported on the carbon support.

[0102] In the first gas-phase reduction step, it is preferable to perform the first gas-phase reduction treatment on a solid obtained by drying a solution containing a carbon support impregnated with a precursor of the first metal. In this case, the temperature at which the solution containing the carbon support impregnated with the precursor of the first metal is dried is not particularly limited as long as the effects of the present invention are obtained, but for example, it may be 40°C or higher, preferably 60°C or higher, more preferably 80°C or higher, and particularly preferably 100°C or higher. Furthermore, this drying temperature may be 200°C or lower, preferably 190°C or lower, more preferably 180°C or lower, even more preferably 170°C or lower, and particularly preferably 160°C or lower. The temperature at which the solution containing the carbon support impregnated with the precursor of the first metal is dried may be determined by arbitrarily combining any of the lower limits and any of the upper limits mentioned above. If the temperature at which the solution containing the carbon support impregnated with the precursor of the first metal is dried is too low, it may take a long time to sufficiently remove the solvent, resulting in the precursor of the first metal adsorbed on the carbon support being desorbed. Furthermore, if the drying temperature of the solution containing the carbon support impregnated with the primary metal precursor is too high, oxidation of the carbon support and / or bumping of the solution may hinder the uniform loading of the primary metal onto the carbon support. For this reason, it is preferable to use a temperature within the range described above when drying the solution containing the carbon support impregnated with the primary metal precursor.

[0103] The first gas-phase reduction treatment is carried out by heating a carbon support impregnated with a precursor of the first metal in a reducing atmosphere. The reducing atmosphere used for the first gas-phase reduction treatment is not particularly limited as long as the effects of the present invention are obtained, but it is preferable to have an atmosphere containing one or more reducing gases selected from the group consisting of hydrogen gas, ammonia gas, and carbon monoxide gas.

[0104] The concentration of the reducing gas in the reducing atmosphere is not particularly limited as long as the effects of the present invention are obtained, but for example, it is preferably 50% by volume or more, more preferably 60% by volume or more, even more preferably 70% by volume or more, even more preferably 80% by volume or more, even more preferably 90% by volume or more, even more preferably 95% by volume or more, and particularly preferably 100% by volume.

[0105] In the first gas-phase reduction treatment, the temperature at which the carbon support impregnated with the precursor of the first metal is heated (hereinafter referred to as the "first reduction heating temperature") is not particularly limited as long as the effects of the present invention are obtained. For example, it is preferably 100°C or higher, more preferably 150°C or higher, even more preferably 200°C or higher, even more preferably 250°C or higher, and particularly preferably 300°C or higher. The first reduction heating temperature may also be, for example, 550°C or lower, preferably 500°C or lower, more preferably 450°C or lower, and particularly preferably 400°C or lower. The first reduction heating temperature may be determined by arbitrarily combining any of the lower limits and any of the upper limits mentioned above. By adopting a temperature within the above range as the first reduction heating temperature, the precursor of the first metal can be efficiently reduced while preventing excessive aggregation of the first metal particles.

[0106] In the first gas-phase reduction treatment, the heating time at the first reduction heating temperature (hereinafter referred to as the "first reduction heating time") is not particularly limited as long as the effects of the present invention are obtained, but for example, it is preferably 10 minutes or more, more preferably 30 minutes or more, even more preferably 60 minutes or more, even more preferably 90 minutes or more, and particularly preferably 100 minutes or more. Also, the first reduction heating time may be, for example, 24 hours or less, preferably 12 hours or less, more preferably 6 hours or less, and particularly preferably 3 hours or less. The first reduction heating time may be determined by arbitrarily combining any of the lower limits and any of the upper limits mentioned above. By adopting a time within the above range as the first reduction heating time, it is possible to sufficiently advance the reduction of the precursor of the first metal while effectively preventing excessive aggregation of the particles of the first metal.

[0107] In the second impregnation step, the first metal-supported catalyst obtained in the first gas-phase reduction step is impregnated with a precursor of the second metal. The second metal is a non-precious metal if the first metal is a precious metal, and a precious metal if the first metal is a non-precious metal.

[0108] Furthermore, if a precious metal precursor is impregnated into the carbon carrier in the first impregnation step described above, it is preferable that the second impregnation step is a step in which a non-precious metal precursor is impregnated into the carbon carrier for the first time after the first impregnation step. Also, if a non-precious metal precursor is impregnated into the carbon carrier in the first impregnation step described above, it is preferable that the second impregnation step is a step in which a precious metal precursor is impregnated into the carbon carrier for the first time after the first impregnation step.

[0109] In this method, when forming a noble metal alloy containing two or more noble metals and / or two or more non-noble metals, in the second impregnation step, as a precursor of the second metal, only one noble metal precursor or only one non-noble metal precursor may be impregnated into the first metal-supported catalyst, or two or more noble metal precursors or two or more non-noble metal precursors may be impregnated into the first metal-supported catalyst. Furthermore, when impregnating the first metal-supported catalyst with two or more precursors of the second metal, the second impregnation step may, for example, first impregnate the first metal-supported catalyst with one of the two or more precursors of the second metal, and then impregnate the first metal-supported catalyst with the other precursor of the second metal, or it may include simultaneously impregnating the first metal-supported catalyst with two or more precursors of the second metal.

[0110] The method for impregnating the first metal-supported catalyst with a metal-second precursor is not particularly limited as long as the effects of the present invention are obtained, but for example, it is preferable to impregnate the first metal-supported catalyst with a solution containing the metal-second precursor. Here, when impregnating the first metal-supported catalyst with two or more metal-second precursors, the second impregnation step may include, for example, first impregnating the first metal-supported catalyst with a solution containing one of the two or more metal-second precursors, and then impregnating the first metal-supported catalyst with a solution containing the other metal-second precursor, or impregnating the first metal-supported catalyst with a solution containing two or more metal-second precursors.

[0111] The atmospheric pressure (atmospheric pressure) in which the second impregnation step is carried out is not particularly limited as long as the effects of the present invention are obtained, and may be normal pressure (atmospheric pressure). However, the second impregnation step preferably includes, for example, holding a solution containing a precursor of the second metal and a catalyst supported by the first metal under reduced pressure. By holding the solution containing the precursor of the second metal and the catalyst supported by the first metal under reduced pressure, the inside of the pores of the catalyst supported by the first metal is effectively degassed, and the precursor is effectively impregnated into the inside of the pores.

[0112] The pressure of the reduced-pressure atmosphere holding the solution containing the metalloid precursor and the metal-supported catalyst is not particularly limited as long as the effects of the present invention are obtained, but for example, it may be -0.02 MPa (minus 0.02 MPa) or less in gauge pressure, preferably -0.04 MkPa or less, more preferably -0.06 MkPa or less, even more preferably -0.08 MPa or less, and particularly preferably -0.10 MPa or less. Alternatively, the pressure of the reduced-pressure atmosphere holding the solution containing the metalloid precursor and the metal-supported catalyst may be, for example, -0.1013 MPa or more in gauge pressure. The pressure of the reduced-pressure atmosphere holding the solution containing the metalloid precursor and the metal-supported catalyst may be determined by any combination of the lower limit and the upper limit described above.

[0113] In the second impregnation step, the time for holding the solution containing the secondary metal precursor and the primary metal-supported catalyst under reduced pressure is not particularly limited as long as the effects of the present invention are obtained, but for example it may be 10 minutes or more, preferably 20 minutes or more, more preferably 30 minutes or more, even more preferably 40 minutes or more, even more preferably 50 minutes or more, and particularly preferably 55 minutes or more. Also, the time for holding the solution containing the secondary metal precursor and the primary metal-supported catalyst under reduced pressure may be, for example, 24 hours or less, 5 hours or less, or 3 hours or less. The time for holding the solution containing the secondary metal precursor and the primary metal-supported catalyst under reduced pressure may be determined by any combination of the lower limit and the upper limit mentioned above.

[0114] Furthermore, the second impregnation step preferably includes holding the solution containing the secondary metal precursor and the primary metal-supported catalyst under pressure. By holding the solution containing the secondary metal precursor and the primary metal-supported catalyst under pressure, the precursor is effectively impregnated into the pores of the carbon support.

[0115] The pressure of the pressurized atmosphere holding the solution containing the metalloid precursor and the metal-first supported catalyst is not particularly limited as long as the effects of the present invention are obtained, but for example, it may be 0.03 MPa or higher in gauge pressure, preferably 0.06 MPa or higher, more preferably 0.09 MPa or higher, even more preferably 0.12 MPa or higher, and particularly preferably 0.15 MPa or higher. Also, the pressure of the pressurized atmosphere holding the solution containing the metalloid precursor and the metal-first supported catalyst may be, for example, 10 MPa or less in gauge pressure, or 5 MPa or less. The pressure of the pressurized atmosphere holding the solution containing the metalloid precursor and the metal-first supported catalyst may be determined by any combination of the lower limit and the upper limit mentioned above.

[0116] In the second impregnation step, the time for holding the solution containing the secondary metal precursor and the primary metal-supported catalyst under pressure is not particularly limited as long as the effects of the present invention are obtained, but for example it may be 10 minutes or more, preferably 20 minutes or more, more preferably 30 minutes or more, even more preferably 40 minutes or more, even more preferably 50 minutes or more, and particularly preferably 55 minutes or more. Also, the time for holding the solution containing the secondary metal precursor and the primary metal-supported catalyst under pressure may be, for example, 24 hours or less, 5 hours or less, or 3 hours or less. The time for holding the solution containing the secondary metal precursor and the primary metal-supported catalyst under pressure may be determined by any combination of the lower limit and the upper limit mentioned above.

[0117] The second impregnation step preferably involves first holding the solution containing the precursor of the second metal and the catalyst supported by the first metal under reduced pressure, and then holding it under pressure. In this case, the precursor of the second metal is impregnated very effectively into the pores of the catalyst supported by the first metal.

[0118] The second impregnation step preferably includes stirring the solution containing the secondary metal precursor and the primary metal-supported catalyst before holding the solution under reduced pressure and / or before holding the solution under pressure. By stirring the solution containing the secondary metal precursor and the primary metal-supported catalyst before holding under reduced pressure and / or before holding under pressure, the precursor is effectively impregnated into the pores of the primary metal-supported catalyst.

[0119] Furthermore, the second impregnation step preferably includes holding the solution containing the secondary metal precursor and the primary metal-supported catalyst under reduced pressure, and / or holding the solution containing the secondary metal precursor and the primary metal-supported catalyst under pressure, and then mixing the solution containing the secondary metal precursor and the primary metal-supported catalyst while stirring. By mixing the solution containing the secondary metal precursor and the primary metal-supported catalyst while stirring after holding under reduced pressure and / or after holding under pressure, the precursor is effectively impregnated into the pores of the primary metal-supported catalyst.

[0120] The time for stirring the solution containing the metalloid precursor and the metalloid-supported catalyst is not particularly limited as long as the effects of the present invention are obtained, but for example it may be 0.1 hours or more, preferably 0.5 hours or more, more preferably 1 hour or more, even more preferably 5 hours or more, even more preferably 10 hours or more, even more preferably 18 hours or more, even more preferably 24 hours or more, even more preferably 35 hours or more, even more preferably 50 hours or more, and especially preferably 65 hours or more. Furthermore, this stirring and mixing time may be, for example, 120 hours or less, 96 hours or less, or 72 hours or less. The time for stirring the solution containing the metalloid precursor and the metalloid-supported catalyst may be determined by any combination of the lower limit and the upper limit mentioned above.

[0121] The ambient temperature (air temperature) in which the second impregnation step is carried out is not particularly limited as long as the effects of the present invention are obtained, and may be room temperature (for example, about 25°C). However, it is preferable that the second impregnation step includes, for example, maintaining a solution containing a precursor of the second metal and a catalyst supported by the first metal at a low temperature. By maintaining a solution containing a precursor of the second metal and a catalyst supported by the first metal at a low temperature, adsorption is promoted by equilibrium shift and / or dissolution of gas molecules is promoted, so that the precursor is effectively impregnated into the pores of the catalyst supported by the first metal.

[0122] In other words, the second impregnation step preferably includes holding the solution containing the metalloid precursor and the metal-supported catalyst under reduced pressure and at a low temperature. Alternatively, the second impregnation step preferably includes holding the solution containing the metalloid precursor and the metal-supported catalyst under pressure and at a low temperature. Alternatively, the second impregnation step preferably includes mixing the solution containing the metalloid precursor and the metal-supported catalyst with stirring at a low temperature before holding the solution containing the metalloid precursor and the metal-supported catalyst under reduced pressure and / or before holding the solution containing the metalloid precursor and the metal-supported catalyst under pressure. Alternatively, the second impregnation step preferably includes mixing the solution containing the metalloid precursor and the metal-supported catalyst with stirring at a low temperature after holding the solution containing the metalloid precursor and the metal-supported catalyst under reduced pressure and / or after holding the solution containing the metalloid precursor and the metal-supported catalyst under pressure.

[0123] In the second impregnation step, the low temperature at which the solution containing the metalloid precursor and the metal-supported catalyst is held is not particularly limited as long as the effects of the present invention are obtained, but is preferably 20°C or lower, more preferably 15°C or lower, even more preferably 10°C or lower, and particularly preferably 5°C or lower. Furthermore, the low temperature at which the solution containing the metalloid precursor and the metal-supported catalyst is held may be, for example, above 0°C or above 1°C. The low temperature at which the solution containing the metalloid precursor and the metal-supported catalyst is held may be determined by arbitrarily combining any of the lower limits and any of the upper limits mentioned above.

[0124] In the second gas-phase reduction step, the first metal-supported catalyst, which was impregnated with a precursor of the second metal in the second impregnation step, is subjected to a gas-phase reduction treatment (hereinafter referred to as the "second gas-phase reduction treatment"), and then an alloying treatment is performed to obtain a metal-supported catalyst on which catalyst metal particles containing an alloy of the first metal and the second metal (i.e., a noble metal alloy, which is an alloy of a noble metal and a non-noble metal) are supported.

[0125] In the second gas-phase reduction step, it is preferable to perform the second gas-phase reduction treatment on a solid obtained by drying a solution containing a first metal-supported catalyst impregnated with a second metal precursor. In this case, the temperature at which the solution containing the first metal-supported catalyst impregnated with a second metal precursor is dried is not particularly limited as long as the effects of the present invention are obtained, but for example, it may be 40°C or higher, preferably 60°C or higher, more preferably 80°C or higher, and particularly preferably 100°C or higher. Furthermore, the temperature at which the solution containing the first metal-supported catalyst impregnated with a second metal precursor is dried may be 200°C or lower, preferably 180°C or lower, more preferably 160°C or lower, even more preferably 140°C or lower, and particularly preferably 110°C or lower. The temperature at which the solution containing the first metal-supported catalyst impregnated with a second metal precursor is dried may be determined by arbitrarily combining any of the lower limits and any of the upper limits described above. If the drying temperature of the solution containing the metal-first metal-supported catalyst impregnated with a metal-second precursor is too low, it may take a long time to sufficiently remove the solvent, resulting in the desorption of the metal-second precursor adsorbed onto the metal-first metal-supported catalyst. Conversely, if the drying temperature of the solution containing the metal-first metal-supported catalyst impregnated with a metal-second precursor is too high, for example, oxidation of the carbon support and / or bumping of the solution may hinder the uniform loading of the metal-second metal onto the carbon support. For this reason, it is preferable to use a temperature within the range described above when drying the solution containing the metal-first metal-supported catalyst impregnated with a metal-second precursor.

[0126] The second gas-phase reduction treatment is carried out by heating a first metal-supported catalyst impregnated with a second metal precursor in a reducing atmosphere. The reducing atmosphere used for the second gas-phase reduction treatment is not particularly limited as long as the effects of the present invention are obtained, but it is preferable to have an atmosphere containing one or more reducing gases selected from the group consisting of hydrogen gas, ammonia gas, and carbon monoxide gas.

[0127] The concentration of the reducing gas in the reducing atmosphere is not particularly limited as long as the effects of the present invention are obtained, but for example, it is preferably 50% by volume or more, more preferably 60% by volume or more, even more preferably 70% by volume or more, even more preferably 80% by volume or more, even more preferably 90% by volume or more, even more preferably 95% by volume or more, and particularly preferably 100% by volume.

[0128] In the second gas-phase reduction treatment, the temperature at which the first metal-supported catalyst impregnated with the second metal precursor is heated (hereinafter referred to as the "second reduction heating temperature") is not particularly limited as long as the effects of the present invention are obtained. For example, it is preferably 500°C or higher, more preferably 550°C or higher, even more preferably 600°C or higher, and particularly preferably 650°C or higher. The second reduction heating temperature may also be, for example, 1300°C or lower, preferably 1100°C or lower, more preferably 1000°C or lower, and particularly preferably 900°C or lower. The second reduction heating temperature may be determined by arbitrarily combining any of the lower limits and any of the upper limits mentioned above. By adopting a temperature within the above range as the second reduction heating temperature, the second metal precursor can be efficiently reduced while preventing excessive aggregation of the second metal particles.

[0129] In the second gas-phase reduction treatment, the heating time at the second reduction heating temperature (hereinafter referred to as the "second reduction heating time") is not particularly limited as long as the effects of the present invention are obtained, but for example, it is preferably 5 minutes or more, more preferably 10 minutes or more, even more preferably 30 minutes or more, even more preferably 40 minutes or more, and particularly preferably 50 minutes or more. The second reduction heating time may also be, for example, 24 hours or less, preferably 12 hours or less, more preferably 6 hours or less, and particularly preferably 3 hours or less. The second reduction heating time may be determined by arbitrarily combining any of the lower limits and any of the upper limits mentioned above. By adopting a time within the above range as the second reduction heating time, it is possible to sufficiently advance the reduction of the secondary metal precursor while effectively preventing excessive aggregation of the secondary metal particles.

[0130] The alloying treatment is carried out by heating a metal-supported catalyst, on which the first and second metals are supported, at the temperature at which an alloy of the first and second metals is formed (hereinafter referred to as the "alloying heating temperature"), after the second gas-phase reduction treatment.

[0131] The alloying heating temperature is not particularly limited as long as the effects of the present invention are obtained, but for example, it is preferably 500°C or higher, more preferably 550°C or higher, even more preferably 600°C or higher, and particularly preferably 650°C or higher. Also, the alloying heating temperature may be, for example, 1300°C or lower, preferably 1100°C or lower, more preferably 1000°C or lower, and particularly preferably 900°C or lower. The alloying heating temperature may be determined by arbitrarily combining any of the lower limits and any of the upper limits mentioned above. By adopting a temperature within the above range as the alloying heating temperature, alloying can be carried out while preventing excessive aggregation of alloy particles.

[0132] In the alloying process, the heating time at the alloying heating temperature (hereinafter referred to as "alloying heating time") is not particularly limited as long as the effects of the present invention are obtained, but for example, it is preferably 5 minutes or more, more preferably 10 minutes or more, even more preferably 30 minutes or more, even more preferably 40 minutes or more, and particularly preferably 50 minutes or more. Also, the alloying heating time may be, for example, 24 hours or less, preferably 12 hours or less, more preferably 6 hours or less, and particularly preferably 3 hours or less. The alloying heating time may be determined by arbitrarily combining any of the lower limits and any of the upper limits mentioned above. By adopting a time within the above range as the alloying heating time, it is possible to effectively prevent excessive aggregation of alloy particles while allowing alloying to proceed sufficiently.

[0133] The atmosphere in which the alloying treatment is performed is not particularly limited as long as the effects of the present invention are obtained, but it is preferably an inert gas atmosphere or a vacuum. The inert gas atmosphere in which the alloying treatment is performed is not particularly limited as long as the effects of the present invention are obtained, but it is preferably an atmosphere containing one or more inert gases selected from the group consisting of nitrogen gas, argon gas, and helium gas.

[0134] The concentration of the inert gas in the inert gas atmosphere is not particularly limited as long as the effects of the present invention are obtained, but for example, it is preferably 50% by volume or more, more preferably 60% by volume or more, even more preferably 70% by volume or more, even more preferably 80% by volume or more, even more preferably 90% by volume or more, even more preferably 95% by volume or more, and particularly preferably 100% by volume.

[0135] In the second gas-phase reduction step, the second reduction heating temperature and the alloying heating temperature may be determined independently, but it is preferable that the second reduction heating temperature is a temperature at which the reduction of the second metal proceeds and at which the alloying of the second metal and the first metal also proceeds.

[0136] In other words, in the second gas-phase reduction step, it is preferable to heat, for example, a first-metal supported catalyst impregnated with a second-metal precursor in a reducing atmosphere at a second reduction heating temperature at which alloying between the first and second metals proceeds. In this case, the reduction of the second-metal precursor and the alloying between the second and first metals can proceed in parallel during the second gas-phase reduction treatment, effectively reducing, for example, the time and cost required for the production of the metal-supported catalyst. Furthermore, by proceeding in parallel with the reduction of the second-metal precursor and the alloying between the second and first metals, the time from the reduction of the precursor to alloying is shortened, effectively suppressing the aggregation of metal particles in the unalloyed state, and as a result, supporting alloy particles having a uniform alloy composition is achieved.

[0137] The second reduction heating temperature at which alloying proceeds is preferably, for example, 500°C or higher, more preferably 550°C or higher, even more preferably 600°C or higher, and particularly preferably 650°C or higher. Furthermore, the second reduction heating temperature at which alloying proceeds may be, for example, 1300°C or lower, preferably 1100°C or lower, more preferably 1000°C or lower, and particularly preferably 900°C or lower. The second reduction heating temperature at which alloying proceeds may be determined by any combination of the lower limit and the upper limit mentioned above.

[0138] Furthermore, alloying in a reducing atmosphere can degrade the carbon support. In this regard, in the second gas-phase reduction process, the second metal is first reduced by performing a second gas-phase reduction treatment in a reducing atmosphere at a second reduction heating temperature where alloying progresses, and then the alloying treatment is performed further in an inert gas atmosphere. This allows for effective alloying of the first metal and the second metal supported on the carbon support while suppressing degradation of the carbon support.

[0139] In the second gas-phase reduction process, the timing of the alloying treatment is not particularly limited as long as it is performed after the second gas-phase reduction process, but it is preferable to perform the second gas-phase reduction process and the alloying treatment consecutively in a single container. That is, in the second gas-phase reduction process, for example, it is preferable to first perform the second gas-phase reduction process in a reducing atmosphere in the container, then replace the reducing atmosphere in the container with an inert gas atmosphere, and then perform the alloying treatment in the inert gas atmosphere in the container.

[0140] In this case, in the second gas-phase reduction step, it is preferable to first perform the second gas-phase reduction treatment at the second reduction heating temperature in a reducing atmosphere inside the container, and then replace the reducing atmosphere inside the container with an inert gas atmosphere while maintaining the temperature inside the container at a temperature difference of 200°C or less from the second reduction temperature, preferably 150°C or less, more preferably 100°C or less, even more preferably 70°C or less, and particularly preferably 50°C or less.

[0141] Furthermore, in this case, it is preferable to replace the reducing atmosphere in the container with an inert gas atmosphere, and then perform the alloying treatment in the inert gas atmosphere in the container at an alloying heating temperature where the difference from the second reduction heating temperature is 200°C or less, preferably 150°C or less, more preferably 100°C or less, even more preferably 50°C or less, even more preferably 30°C or less, and particularly preferably 10°C or less.

[0142] This method may further include a post-treatment step after the second gas-phase reduction step. In the post-treatment step, the metal-supported catalyst obtained in the second gas-phase reduction step is subjected to a treatment to remove excess metal and / or a treatment to remove noble metal oxides. The treatment to remove excess metal is not particularly limited as long as the effects of the present invention are obtained, but is preferably a washing treatment using an acid such as nitric acid. The treatment to remove noble metal oxides is not particularly limited as long as the effects of the present invention are obtained, but is preferably a heat treatment in an inert gas atmosphere such as a nitrogen atmosphere. In the post-treatment step, heat treatment of the metal-supported catalyst in an inert gas atmosphere removes oxides from the metal surface generated in the treatment to remove excess metal and / or reduces the surface roughness of the metal, contributing to improved durability and / or catalytic function.

[0143] The temperature at which the metal-supported catalyst is heated in an inert gas atmosphere during the post-treatment process (hereinafter referred to as the "post-treatment heating temperature") is not particularly limited as long as the effects of the present invention are obtained, but is preferably 500°C or higher, more preferably 550°C or higher, even more preferably 600°C or higher, and particularly preferably 650°C or higher. The post-treatment heating temperature may also be, for example, 1300°C or lower, preferably 1100°C or lower, more preferably 1000°C or lower, and particularly preferably 900°C or lower. The post-treatment heating temperature may be determined by arbitrarily combining any of the lower limits and any of the upper limits mentioned above.

[0144] The method may further include an impregnation step and / or a gas-phase reduction step. That is, the method may further include, for example, a third impregnation step in which a precursor of a first metal, a second metal, or a third metal of a different type from the first and second metals is further impregnated after the second gas-phase reduction step described above, and a third gas-phase reduction step in which a gas-phase reduction treatment and alloying treatment are further performed after the third impregnation step. In this case, the third impregnation step is not particularly limited as long as the effects of the present invention are obtained, but it is preferable to perform it in the same manner as the first or second impregnation step described above. Also, the third gas-phase reduction step is not particularly limited as long as the effects of the present invention are obtained, but it is preferable to perform it in the same manner as the first or second gas-phase reduction step described above.

[0145] According to this method, a metal-supported catalyst is produced that possesses a high precious metal content while also exhibiting excellent durability and superior catalytic function. In other words, the catalyst described above is preferably produced by this method.

[0146] The electrode according to this embodiment (hereinafter referred to as "the electrode") includes the catalyst. That is, the electrode is a battery electrode comprising, for example, an electrode substrate and the catalyst supported on the electrode substrate. The electrode is preferably a battery electrode. That is, the electrode is preferably an electrode for a fuel cell (e.g., a polymer electrolyte fuel cell), an air battery, a water electrolytic cell (e.g., a polymer electrolyte water electrolytic cell), a redox flow battery, or a halogen battery.

[0147] This electrode may be a cathode or an anode, but it is preferably a cathode. That is, this electrode is the cathode or anode of a fuel cell, air battery, water electrolytic cell, redox flow battery, or halogen battery, and is preferably a cathode.

[0148] The battery according to this embodiment (hereinafter referred to as "the battery") includes the electrode. Specifically, the battery is preferably a fuel cell (e.g., a polymer electrolyte fuel cell), an air battery, a redox flow battery, or a halogen battery that includes the electrode. The battery is preferably a membrane / electrode assembly (MEA) that includes the electrode.

[0149] This battery is a battery having this electrode as the cathode or anode, preferably a battery having this electrode as the cathode. That is, this battery is a fuel cell, air battery, redox flow battery, or halogen battery having this electrode as the cathode or anode, preferably a fuel cell, air battery, redox flow battery, or halogen battery having this electrode as the cathode.

[0150] Next, a specific example of this embodiment will be described. [Examples]

[0151] [Manufacturing of carbon carriers] 1.0 g of polyacrylonitrile (PAN), 1.0 g of 2-methylimidazole, 6.0 g of zinc chloride (ZnCl2), and 30 g of dimethylformamide were mixed. The solvent was removed from the resulting mixture by drying. The dried mixture was heated in an air atmosphere and infusible at 250°C.

[0152] The mixture, after being rendered infusible, was carbonized by heating it at 1500°C under a nitrogen atmosphere and a gauge pressure of 0.90 MPa. Dilute hydrochloric acid was added to the carbonized material obtained by carbonization and the mixture was stirred. Subsequently, the suspension containing the carbonized material was filtered using a filtration membrane, and the carbonized material was washed with distilled water until the filtrate became neutral. Thus, metal removal treatment was performed by acid washing.

[0153] The carbonized material, after metal removal treatment, was pulverized using a fine grinder until the median particle size was 0.4 μm or less. The pulverized carbonized material was then vacuum-dried to remove moisture. Subsequently, the carbonized material was heat-treated at 300°C in a nitrogen atmosphere. Furthermore, the resulting carbonized material was graphitized by heating at 2000°C under atmospheric pressure in a nitrogen atmosphere. The resulting carbonized material was then used as a carbon support.

[0154] [Manufacturing of metal-supported catalysts] In Example 1 and Example C1, catalyst metal particles were supported on a carbon carrier by the following gas-phase reduction method. First, the first impregnation step was performed. Specifically, 1 g of carbon carrier and 22.2 g of an aqueous solution containing chloroplatinic acid (H2PtCl6), a platinum precursor, in an amount that resulted in a platinum concentration of 5% by weight (platinum content of 1.11 g) were stirred and mixed for 1 hour. The mixed solution was first held under reduced pressure of -0.10 MPa or less (specifically, -0.10 MPa to -0.1013 MPa) for 1 hour, then held under increased pressure of 0.15 MPa or more (specifically, 0.15 MPa to 0.20 MPa) for 1 hour, and then stirred and mixed for 66 hours. This first impregnation step was carried out while maintaining the temperature of the mixed solution at 5°C or less (specifically, 0°C to 5°C).

[0155] Next, a first gas-phase reduction process was carried out. Specifically, the mixture obtained in the first impregnation process was dried under vacuum at 100°C, and then held at 150°C in a nitrogen atmosphere to volatilize the solvent components. The resulting solid was subjected to a heat treatment (first gas-phase reduction treatment) at 350°C for 120 minutes in a hydrogen atmosphere (100% hydrogen gas by volume) to obtain a platinum-supported catalyst.

[0156] Next, the second impregnation step was carried out. Specifically, 2.1 g of the platinum-supported catalyst obtained in the first gas-phase reduction step and 20 g of an aqueous solution containing cobalt chloride (CoCl2), a cobalt precursor, in an amount that resulted in a cobalt concentration of 0.56% by weight (cobalt content of 0.112 g) were stirred and mixed for 1 hour. The mixed solution was first held under reduced pressure of -0.10 MPa or less (specifically, -0.10 MPa to -0.1013 MPa) for 1 hour, then held under increased pressure of 0.15 MPa or more (specifically, 0.15 MPa to 0.20 MPa) for 1 hour, and then stirred and mixed for 18 hours. This second impregnation step was carried out while maintaining the temperature of the mixed solution at 5°C or less (specifically, 0°C to 5°C).

[0157] Next, a second gas-phase reduction process was carried out. Specifically, the mixture obtained in the second impregnation process was dried under vacuum at 100°C. The resulting solid was subjected to a heat treatment (second gas-phase reduction treatment) at 700°C for 60 minutes in a hydrogen atmosphere (100% hydrogen gas by volume), and then, while maintaining the atmosphere temperature within the range of 650 to 750°C, the hydrogen atmosphere was replaced with a nitrogen atmosphere (100% nitrogen gas by volume), and the solid was subjected to a heat treatment (alloying treatment) at 700°C for 120 minutes in the nitrogen atmosphere to obtain a platinum alloy-supported catalyst.

[0158] Next, a post-treatment process was carried out. Specifically, in order to remove excess metal from the platinum alloy-supported catalyst obtained in the second gas-phase reduction process, the platinum alloy-supported catalyst was mixed with a 10% nitric acid solution for 2 hours. After that, the platinum alloy-supported catalyst and the acid solution were separated by filtration, and the platinum alloy-supported catalyst was further washed with distilled water until the filtrate was neutral. The washed platinum alloy-supported catalyst was dried in a vacuum at 60°C to remove moisture.

[0159] Subsequently, to remove nitric acid, the platinum alloy-supported catalyst was heat-treated at 300°C in nitrogen. Furthermore, to reduce and remove platinum oxide, the platinum alloy-supported catalyst was heat-treated at 700°C in nitrogen. In this way, a metal-supported catalyst containing a carbon support and platinum and cobalt alloy particles supported on the carbon support was obtained.

[0160] In Example 2, a metal-supported catalyst was obtained in the same manner as in Example 1 and other cases described above, except that in the second impregnation step, 20 g of an aqueous solution containing cobalt chloride in an amount that resulted in a cobalt concentration of 0.32% by weight (cobalt content of 0.064 g) was used, and the procedure was the same as in Example 1 and other cases described above. The catalyst included a carbon support and alloy particles of platinum and cobalt supported on the carbon support.

[0161] In Example 3, a metal-supported catalyst containing a carbon support and platinum and cobalt alloy particles supported on the carbon support was obtained in the same manner as in Example 1 and other cases described above, except that the first and second impregnation steps were carried out while maintaining the temperature of the mixed solution at 25°C.

[0162] In Example 4, a metal-supported catalyst containing a carbon support and platinum and cobalt alloy particles supported on the carbon support was obtained in the same manner as in Example 1 and other cases described above, except that the mixture was held under reduced pressure and under pressure for 1 hour each, and then stirred for 18 hours instead of 66 hours.

[0163] In Example 5, a metal-supported catalyst was obtained in the same manner as in Example 1 and other cases described above, except that in the second impregnation step, 20 g of an aqueous solution containing cobalt chloride in an amount that resulted in a cobalt concentration of 0.23% by weight (cobalt content of 0.045 g) was used, and the procedure was the same as in Example 1 and other cases described above. The catalyst included a carbon support and platinum and cobalt alloy particles supported on the carbon support.

[0164] In Example 6, a metal-supported catalyst was obtained in the same manner as in Example 1 and above, except that in the second impregnation step, instead of using an aqueous solution containing cobalt chloride, 20 g of an aqueous solution containing nickel chloride hexahydrate (NiCl2·6H2O) in an amount that resulted in a nickel concentration of 0.56% by weight (nickel content of 0.111 g) was used, and the procedure was the same as in Example 1 and above. The catalyst included a carbon support and platinum-nickel alloy particles supported on the carbon support.

[0165] In Example 7, a metal-supported catalyst was obtained in the same manner as in Example 1 and above, except that in the second impregnation step, instead of using an aqueous solution containing cobalt chloride, 20 g of an aqueous solution containing nickel hexahydrate (NiCl2·6H2O) and manganese chloride tetrahydrate (MnCl2·4H2O) was used in an amount that resulted in a nickel concentration of 0.278% by weight (nickel content of 0.056 g) and a manganese concentration of 260% by weight (manganese content of 0.052 g). The procedure was the same as in Example 1 and above.

[0166] In Example 8, the first impregnation step was carried out in the same manner as in Example 1 and others, except that 17.8 g of an aqueous solution containing chloroplatinic acid in an amount that resulted in a platinum concentration of 5% by weight (platinum content of 0.89 g) was used first. Subsequently, the first gas-phase reduction step, the second impregnation step, and the second gas-phase reduction step were carried out in the same manner as in Example 1 and others.

[0167] Next, the third impregnation step was carried out. Specifically, 1.99 g of the platinum alloy-supported catalyst obtained in the second gas-phase reduction step and 22.2 g of an aqueous solution containing chloroplatinic acid in an amount that resulted in a platinum concentration of 1% by weight (platinum content of 0.22 g) were stirred and mixed for 1 hour. The mixed solution was first held under reduced pressure of -0.10 MPa or less (specifically, -0.10 MPa to -0.1013 MPa) for 1 hour, then held under increased pressure of 0.15 MPa or more (specifically, 0.15 MPa to 0.20 MPa) for 1 hour, and then stirred and mixed for 66 hours. This third impregnation step was carried out while maintaining the temperature of the mixed solution at 5°C or below.

[0168] Next, a third gas-phase reduction process was carried out. Specifically, the mixture obtained in the third impregnation process was dried in a vacuum at 100°C, and then held in a nitrogen atmosphere at 150°C to volatilize the solvent components. The obtained solid was subjected to a heat treatment (gas-phase reduction treatment) at 700°C for 60 minutes in a hydrogen atmosphere (100% hydrogen gas), and then, while maintaining the atmosphere temperature within the range of 650-750°C, the hydrogen atmosphere was replaced with a nitrogen atmosphere (100% nitrogen gas), and the solid was subjected to a heat treatment (alloying treatment) at 700°C for 120 minutes in the nitrogen atmosphere. After that, a post-treatment process was carried out in the same manner as in Example 1 above to obtain a metal-supported catalyst containing a carbon support and alloy particles of platinum and cobalt supported on the carbon support.

[0169] In Example 9, a metal-supported catalyst containing a carbon support and platinum and cobalt alloy particles supported on the carbon support was obtained in the same manner as in Example 1 and the like, except that in the first and second impregnation steps, the mixed solution was held under atmospheric pressure for 2 hours instead of being held under reduced pressure for 1 hour and under pressure for 1 hour.

[0170] In Example 10, a metal-supported catalyst was obtained in the same manner as in Example 1 and above, except that 1000°C was used instead of 700°C as the heating temperature in the hydrogen and nitrogen atmospheres during the second gas-phase reduction step. The catalyst included a carbon support and platinum and cobalt alloy particles supported on the carbon support.

[0171] In Example C1, a metal-supported catalyst was obtained in the same manner as in Example 1 and other examples above, except that 9.0 g of an aqueous solution containing chloroplatinic acid in an amount that resulted in a platinum concentration of 5% by weight (platinum content of 0.45 g) was used in the first impregnation step. The catalyst included a carbon support and alloy particles of platinum and cobalt supported on the carbon support.

[0172] In Example C2, a metal-supported catalyst containing a carbon carrier and alloy particles of platinum and cobalt supported on the carbon carrier was obtained in the same manner as in Example 1, etc., except that in the first impregnation step, instead of using an aqueous solution containing chloroplatinic acid, 42.2 g of an aqueous solution containing chloroplatinic acid and cobalt chloride in an amount that resulted in a platinum concentration of 5% by weight (platinum content of 1.1 g) and a cobalt concentration of 0.56% by weight (cobalt content of 0.112 g), in the first impregnation step, the mixed solution was held at atmospheric pressure for 2 hours instead of being held under reduced pressure for 1 hour and under pressure for 1 hour in the first and second impregnation steps, and the second impregnation step and second gas-phase reduction step were not performed.

[0173] In Example C3, a metal-supported catalyst was obtained in the same manner as in Example 1 and other cases described above, except that 500°C was used instead of 700°C as the heating temperature in the hydrogen atmosphere and nitrogen atmosphere during the second gas-phase reduction step. The catalyst consisted of a carbon support and platinum and cobalt alloy particles supported on the carbon support.

[0174] In Example C4, catalyst metal particles were supported on a carbon support by the following liquid-phase reduction method. First, the first impregnation step was performed. Specifically, 1 g of carbon support and 22.2 g of an aqueous solution containing chloroplatinic acid in an amount that resulted in a platinum concentration of 5% by weight (platinum content of 1.11 g) were stirred and mixed for 1 hour. The mixed solution was first held under reduced pressure of -0.10 MPa or less (specifically, -0.10 MPa to -0.1013 MPa) for 1 hour, then held under increased pressure of 0.15 MPa or more (specifically, 0.15 MPa to 0.20 MPa) for 1 hour, and then stirred and mixed for 66 hours. This first impregnation step was carried out while maintaining the temperature of the mixed solution at 5°C or less (specifically, 0°C to 5°C).

[0175] Next, the first liquid-phase reduction process was carried out. Specifically, ethylene glycol was added as a reducing agent to the mixture obtained in the first impregnation process, and the mixture was held in air at 80°C for 4 hours to perform a liquid-phase reduction treatment and obtain a platinum-supported catalyst.

[0176] Next, the second impregnation process was carried out. Specifically, the mixture obtained in the first liquid-phase reduction process was dried in a vacuum at 100°C, and then held in nitrogen at 150°C to volatilize the solvent components. 2.0 g of the resulting platinum-supported catalyst and 20 g of an aqueous solution containing cobalt chloride in an amount that resulted in a cobalt concentration of 0.56% by weight (cobalt content of 0.112 g) were stirred and mixed for 1 hour. The mixed solution was held under reduced pressure of -0.10 MPa or less (specifically, -0.10 MPa to -0.1013 MPa) for 1 hour, then held under increased pressure of 0.15 MPa or more (specifically, 0.15 MPa to 0.20 MPa) for 1 hour, and then stirred and mixed for 18 hours. This second impregnation process was carried out while maintaining the temperature of the mixed solution at 5°C or less (specifically, 0°C to 5°C).

[0177] Next, a second liquid-phase reduction process was carried out. Specifically, ethylene glycol was added as a reducing agent to the mixture obtained in the second impregnation process, and the mixture was held in air at 80°C for 4 hours to perform the liquid-phase reduction treatment.

[0178] Next, an alloying process was carried out. Specifically, the mixture obtained in the second liquid-phase reduction process was dried in a vacuum at 100°C. The resulting solid was subjected to a heat treatment (alloying treatment) at 700°C for 60 minutes in a hydrogen atmosphere (100% hydrogen gas by volume), and then, while maintaining the atmosphere temperature within the range of 650 to 750°C, the hydrogen atmosphere was replaced with a nitrogen atmosphere (100% nitrogen gas by volume), and the solid was subjected to a heat treatment at 700°C for 120 minutes in the nitrogen atmosphere to obtain a platinum alloy-supported catalyst.

[0179] Next, a post-treatment process was carried out. Specifically, to remove excess metal from the platinum alloy-supported catalyst obtained in the alloying process, the platinum alloy-supported catalyst was mixed with a 10% nitric acid solution for 2 hours. After that, the platinum alloy-supported catalyst and the acid solution were separated by filtration, and the platinum alloy-supported catalyst was further washed with distilled water until the filtrate was neutral. The washed platinum alloy-supported catalyst was dried in a vacuum at 60°C to remove moisture.

[0180] Subsequently, to remove nitric acid, the platinum alloy-supported catalyst was heat-treated at 300°C in nitrogen. Furthermore, to reduce and remove platinum oxide, the platinum alloy-supported catalyst was heat-treated at 700°C in nitrogen. In this way, a metal-supported catalyst containing a carbon support and platinum and cobalt alloy particles supported on the carbon support was obtained.

[0181] [Raman spectroscopy] The metal-supported catalyst was analyzed by Raman spectroscopy. The Raman spectra were measured using the HORIBA micro-laser Raman spectroscopy system (LabRAM, HORIBA Jobin Yvon). The laser used for the measurement had an excitation wavelength of 532 nm, an output of 50 mW, and was measured through a light-reducing filter D3 under conditions of 90 seconds of exposure × 2 integrations to obtain the Raman spectra.

[0182] Baseline correction was applied to the obtained Raman spectra. That is, Raman shift (cm) -1 ) is 600cm -1 Scattering intensity in the vicinity and 2000 cm -1 A straight line connecting the scattering intensities of the vicinity was determined as the baseline, and baseline correction was performed by subtracting this baseline from each intensity in the scattering spectrum.

[0183] Next is the Raman shift, 1340cm -1 Nearby (specifically, 1320cm) -1 Above, 1360cm -1 We identified the D band with a peak top within the following range. Then, the intensity of the D band I d (Raman shift (cm) corresponding to the intensity of the peak top of the D band) -1 )A d Therefore, the intensity of the D band I d Raman shift (cm) corresponding to half the intensity -1 )B d By subtracting this, the Raman D half-width at half maximum (cm) -1 The Raman D half-width (cm) was calculated. Specifically, the Raman D half-width of the metal-supported catalyst was calculated using the following formula: Raman D half-width (cm) -1 )=A d (cm-1 ) - B d (cm -1 )。

[0184] Next, the G band having a peak top in the vicinity of a Raman shift of 1600 cm -1 (specifically, 1550 cm -1 or higher and 1700 cm -1 or lower) and the 2D band having a peak top in the vicinity of a Raman shift of 2680 cm -1 (specifically, 2600 cm -1 or higher and​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​[Metal content: Inductively coupled plasma atomic emission spectroscopy] The platinum and non-platinum metal (metals other than platinum) content of the metal-supported catalyst was measured by inductively coupled plasma atomic emission spectroscopy (ICP-OES). Specifically, 100 mg of the metal-supported catalyst was first heated and held at 800°C in an air atmosphere for 3 hours to remove non-metallic components from the catalyst.

[0187] Next, the metal-supported catalyst was immersed in 5 mL of aqua regia and heated at 50°C for 1 hour to dissolve the metal contained in the catalyst. Furthermore, distilled water was added to dilute the solution to a volume of 50 mL to obtain a metal solution. Subsequently, the platinum concentration and non-platinum metal concentration of the obtained metal solution were measured using a sequential plasma emission spectrometer (ICPS-8100, manufactured by Shimadzu Corporation).

[0188] Then, by multiplying the platinum concentration (mg / mL) and non-platinum metal concentration (mg / mL) of the metal solution by the volume of the metal solution (50 mL), the weight of platinum (mg) and the weight of non-platinum metal (mg) per 100 mg of metal-supported catalyst were obtained.

[0189] Furthermore, the platinum content (weight %) and non-platinum metal content (weight %) obtained by ICP-OES were calculated by dividing the weight of platinum (mg) and non-platinum metal (mg) contained in the metal-supported catalyst by the weight of the metal-supported catalyst, which is 100 mg, and then multiplying by 100. In addition, the sum of the platinum content (weight %) and non-platinum metal content (weight %) of the metal-supported catalyst was obtained as the metal content (weight %) of the metal-supported catalyst.

[0190] [Specific surface area and average pore diameter] The specific surface area and average pore diameter of metal-supported catalysts were measured using the nitrogen adsorption method with a specific surface area / pore distribution analyzer (TriStar II 3020, manufactured by Shimadzu Corporation) and its accompanying analysis software (TriStar II 3020).

[0191] In other words, first, 0.1 g of metal-supported catalyst is heated at 100°C, 6.7 × 10⁻⁶-2 By holding the metal-supported catalyst at Pa for 3 hours, the water adsorbed on it was removed. Next, at a temperature of 77K, the change in the amount of nitrogen adsorbed onto the metal-supported catalyst in response to a change in nitrogen gas pressure was measured to obtain a nitrogen adsorption isotherm at 77K.

[0192] Then, using the nitrogen adsorption isotherm at a temperature of 77K, the BET specific surface area (m²) of the metal-supported catalyst by nitrogen adsorption was determined. 2 The BET specific surface area (m²) of the metal-supported catalyst was obtained. 2 Based on the BET specific surface area (m²) per gram of carbon support contained in the metal-supported catalyst, obtained by the above-mentioned ICP-OES, the BET specific surface area (m²) per gram of carbon support contained in the metal-supported catalyst is calculated. 2 The weight ratio of carbon support ( / g - carbon support) was calculated. Specifically, the weight ratio of carbon support contained in the metal-supported catalyst was first calculated using the following formula: Weight ratio of carbon support = 1 - (Metal content obtained by ICP-OES (weight %)) / 100. Next, the BET specific surface area (m²) of the metal-supported catalyst was calculated using the obtained weight ratio of carbon support. 2 By dividing by ( / g), the BET specific surface area (m²) per gram of carbon support can be calculated. 2 The amount of carbon support ( / g) was calculated. In addition, the total pore volume (cm³) of the metal-supported catalyst was calculated from the amount of adsorption at the point where the relative pressure P / P0 was 0.98 on the nitrogen adsorption isotherm at a temperature of 77K. 3 / g) was obtained.

[0193] Then, using the analysis software attached to the specific surface area and pore distribution measuring device, the average pore diameter (nm) of the metal-supported catalyst was calculated using the following formula: Average pore diameter (nm) = 4 × {Total pore volume (cm³)} 3 ( / g) × 10 21} / {specific surface area(m 2 ( / g) × 10 18}.

[0194] [Alloy composition heterogeneity] The alloy composition heterogeneity was calculated using the following equation (I), based on the measured lattice constant of the platinum alloy contained in the metal-supported catalyst, determined by powder X-ray diffraction (XRD) of the metal-supported catalyst, and the theoretical lattice constant of the platinum alloy contained in the metal-supported catalyst, determined by ICP-OES of the metal-supported catalyst. Specifically, the alloy composition heterogeneity was calculated by subtracting the value obtained by dividing the theoretical lattice constant by the measured lattice constant from 1, and then multiplying by 100. JPEG2023129139000008.jpg11170

[0195] The measured lattice constant of the platinum alloy contained in the metal-supported catalyst was determined using Bragg's equation from the XRD pattern obtained by powder X-ray diffraction of the metal-supported catalyst. Specifically, XRD measurements were performed using an X-ray diffractometer (Rigaku RINT2100 / PC, Rigaku Corporation). The applied voltage and current to the X-ray tube were 50kV and 300mA, respectively. The sampling interval was 0.1°, the scanning speed was 1° / min, and the measurement angle range (2θ) was 5 to 90°. CuKα was used as the incident X-ray. The sample thickness was 0.5 mm, and the divergence slit width β was 2 / 3°.

[0196] The lattice plane spacing was calculated using Bragg's equation from the position of the peak top (diffraction angle 2θ) of the diffraction peak corresponding to the (111) plane of the platinum alloy, where the diffraction angle 2θ of the obtained XRD figure appears in the range of 39° to 44°, using the following Bragg's equation: 2dsinθ = nλ. In this Bragg's equation, d is the lattice plane spacing, θ is the X-ray incidence angle, λ is the X-ray incidence wavelength, and n is an integer.

[0197] Then, the lattice constant (measured lattice constant) a was calculated using the following relationship between lattice plane spacing and plane index: d = a / (h 2 +k 2 +l 2 ) 0.5 In this equation relating the lattice plane spacing and the plane index, d is the lattice plane spacing, a is the lattice constant (experimental lattice constant), and h, k, and l are the plane indexes.

[0198] The theoretical lattice constant of the platinum alloy contained in the metal-supported catalyst was calculated using Vegard's law after determining the mole fractions of platinum and non-platinum metals by ICP-OES measurement. Vegard's law is an empirical rule that shows the relationship between the composition of an alloy and its lattice constant, and the lattice constant (theoretical lattice constant) a of the alloy is calculated by the following equation (V). JPEG2023129139000009.jpg12170

[0199] In equation (V) above, a on the left side is the lattice constant of the alloy (theoretical lattice constant), and N is the mole fraction of each metal (for example, N A , N B and N c (where a is the mole fraction of metal A, metal B, and metal C, respectively), and a on the right side is the lattice constant of each metal in its elemental form (for example, a A a B and a c (where a is the lattice constant of metal A, metal B, and metal C in their individual components, respectively). Specifically, for example, if an alloy is composed of two types of metals, namely metal A and metal B, the theoretical lattice constant a of the alloy is calculated by the following equation: a = N A a A +N B a B Furthermore, if the alloy is composed of three types of metals, namely metal A, metal B, and metal C, the theoretical lattice constant a of the alloy can be calculated using the following formula: a = N A a A +N B a B +N c a c Furthermore, if the alloy is composed of four or more types of metals, the right-hand side of the above equation (V) will have terms for the fourth and subsequent types of metals, "N X a X The following is added: (X indicates the type of metal.)

[0200] The molar fraction of each metal was determined by measuring the metal content of the metal-supported catalyst using ICP-OES. That is, the platinum content (wt%) and the content (wt%) of one or more non-platinum metals obtained by ICP-OES as described above were divided by the atomic weight of each metal species to calculate the molar amounts of platinum and each of the one or more non-platinum metals. Then, the molar fraction of each metal species was calculated by dividing the molar amount of each metal species by the total of the molar amounts of all metal species. By substituting the molar fraction obtained in this way into the equation of Vegard's law, the theoretical lattice constant of the platinum alloy was determined.

[0201] [Half-value asymmetry and quarter-value asymmetry] Based on the XRD pattern of the metal-supported catalyst obtained as described above, the half-value asymmetry and the quarter-value asymmetry were determined by the following equations (II) and (III), respectively. JPEG2023129139000010.jpg11170JPEG20231291390000.jpg10170

[0202] Equations (II) and (III) will be explained while referring to the typical XRD pattern shown in Figure m 2. As shown in Figure 2, D M is the value of the diffraction angle 2θ at which the diffraction line shows the maximum intensity I Lh in the range of the diffraction angle 2θ of the XRD pattern of the metal-supported catalyst from 35° to 44° (the range of the diffraction angle 2θ at which the diffraction peak of the (111) plane of the platinum alloy appears), and D M is the smallest value of the diffraction angle 2θ showing the intensity I h which is half of the maximum intensity I Hh in the range of the diffraction angle 2θ from 35° to 44°, and D M is the largest value of the diffraction angle 2θ showing the intensity I h which is half of the maximum intensity I Lq in the range of the diffraction angle 2θ from 35° to 44°, and D M is the intensity I qThis is the smallest diffraction angle 2θ value among the diffraction angles 2θ that exhibit this characteristic, and D Hq In this case, the diffraction line has maximum intensity I when the diffraction angle 2θ is in the range of 35° to 44°. M One-quarter of the intensity I q This is the largest diffraction angle 2θ value among those that exhibit this property.

[0203] Figures 3A and 3B show the XRD patterns obtained for the metal-supported catalysts of Example 1 and Example 5, respectively. Figures 4A and 4B show the XRD patterns obtained for the metal-supported catalysts of Example C2 and Example C4, respectively.

[0204] [Platinum / Non-platinum metal molar ratio] The ratio of the molar amount of platinum to the molar amount of non-platinum metal constituting the platinum alloy particles supported on the metal-supported catalyst (Pt / M molar ratio) was calculated by dividing the mole fraction of platinum, obtained by ICP-OES as described above, by the mole fraction of the non-platinum metal.

[0205] [Number-average particle size and volume-average particle size of catalyst metal particles: Powder X-ray diffraction] Powder X-ray diffraction (XRD) was used to measure the number-average particle size (nm) and volume-average particle size (nm) of catalyst metal particles supported on a carbon support in a metal-supported catalyst. Specifically, a sample of the powdered metal-supported catalyst was first placed in a recess (2 cm × 2 cm × 0.5 mm thick) of a glass sample plate and held down with a glass slide, ensuring that the sample was uniformly packed into the recess so that its surface aligned with the reference plane. Next, the glass sample plate was fixed to a wide-angle X-ray diffraction sample stage to prevent the shape of the packed sample from collapsing.

[0206] Powder X-ray diffraction measurements were then performed using an X-ray diffractometer (Rigaku RINT2100 / PC, Rigaku Corporation). The applied voltage and current to the X-ray tube were 50kV and 300mA, respectively. The sampling interval was 0.1°, the scanning speed was 1° / min, and the measurement angle range (2θ) was 5 to 90°. CuKα was used as the incident X-ray. The sample thickness was 0.5 mm, and the divergence slit width β was 2 / 3°.

[0207] The obtained XRD pattern was subjected to peak separation using a Gaussian function as described below, and the crystallite size corresponding to each peak obtained through peak separation was determined using Scherrer's formula. The number of crystallites was then calculated, i.e., "peak area ratio / crystallite size". 3 The number-average particle diameter of the catalyst metal particles was calculated using a weighted average with "" as the weight. On the other hand, the volume-average particle diameter of the catalyst metal particles was calculated using a weighted average with the obtained crystallite diameter and volume, i.e., "peak area ratio", as the weight.

[0208] Here, we will explain in more detail how to determine the number-average particle diameter (nm) and the volume-average particle diameter (nm). For metal-supported catalysts in which platinum alloy particles are supported as catalytic metal particles, the (111) diffraction line of the platinum alloy appears in the XRD figure obtained by powder X-ray diffraction using CuKα rays at a diffraction angle (2θ) around 40° (for example, within the range of 35° to 44°). This diffraction line includes diffraction lines originating from pure platinum, diffraction lines originating from the platinum alloy, and diffraction lines originating from the carbon structure of the carbon support.

[0209] Diffraction lines originating from pure platinum are defined as diffraction lines with a peak top at a diffraction angle (2θ) of 39.6° or greater and less than 39.8°. Diffraction lines originating from platinum alloys are defined as diffraction lines with a peak top at a diffraction angle (2θ) of 39.9° or greater and less than 43.0°. Diffraction lines originating from the carbon structure of a carbon support are defined as diffraction lines with a peak top at a diffraction angle (2θ) of 43.3° or greater and less than 43.7°.

[0210] When a metal-supported catalyst contains multiple types of platinum alloys with different compositions and / or crystal structures, multiple diffraction lines originating from the platinum alloys will appear. The diffraction angle at which the peak top of the diffraction line originating from the platinum alloy is located is determined by its composition and crystal structure.

[0211] For example, composition Pt XDiffraction lines originating from platinum-cobalt alloys represented by Co(X=1~20) are defined as diffraction lines with a peak top at a diffraction angle between 39.9° and less than 41.8°. Composition: Pt X Diffraction lines originating from platinum-nickel alloys represented by Ni (X=1~20) are defined as diffraction lines with a peak top at a diffraction angle between 39.9° and 42.0°. Composition: Pt X Diffraction lines originating from a platinum-nickel-manganese alloy represented as Ni1Mn1(X=2~40) are defined as diffraction lines having a peak top at a diffraction angle between 39.9° and 41.2°.

[0212] Specifically, for example, diffraction lines originating from a platinum-cobalt alloy represented by the composition PtCo are defined as diffraction lines with a peak top at a diffraction angle of 41.4° or greater and less than 41.8°. Similarly, diffraction lines originating from a platinum-cobalt alloy represented by the composition Pt3Co are defined as diffraction lines with a peak top at a diffraction angle of 40.3° or greater and less than 41.2°. Furthermore, diffraction lines originating from a platinum-cobalt alloy represented by the composition Pt7Co are defined as diffraction lines with a peak top at a diffraction angle of 39.9° or greater and less than 40.3°.

[0213] Furthermore, for example, diffraction lines originating from a platinum-nickel alloy represented by the composition PtNi are defined as diffraction lines having a peak top at a diffraction angle of 41.6° or greater and less than 42.0°. Also, diffraction lines originating from a platinum-nickel alloy represented by the composition Pt3Ni are defined as diffraction lines having a peak top at a diffraction angle of 40.4° or greater and less than 41.2°. Also, diffraction lines originating from a platinum-nickel alloy represented by the composition Pt7Ni are defined as diffraction lines having a peak top at a diffraction angle of 39.9° or greater and less than 40.3°. Diffraction lines originating from a platinum-nickel-manganese alloy represented by the composition Pt6Ni1Mn1 are defined as diffraction lines having a peak top at a diffraction angle of 40.1° or greater and less than 40.8°.

[0214] Furthermore, when a metal-supported catalyst contains multiple types of platinum particles with the same composition and crystal structure but different crystallite sizes, multiple diffraction lines appear that have peak tops at approximately the same diffraction angle and have different full widths at half maximum.

[0215] In fact, in the XRD patterns obtained for the metal-supported catalyst, the (111) diffraction line of the platinum alloy appeared at a diffraction angle (2θ) of around 40°. Therefore, baseline correction was first performed. Specifically, a straight line connecting the diffraction intensities at diffraction angles (2θ) of 35° to 37° and the diffraction intensities at 50° to 52° was determined as the baseline, and baseline correction was performed by subtracting this baseline from each intensity of the diffraction line.

[0216] Next, the baseline-corrected diffraction lines were separated into peaks originating from one or more types of pure platinum and / or one or more types of platinum alloys, and peaks originating from carbon. The separation of diffraction lines was performed by assuming that each of the multiple peaks obtained by the separation is represented by a Gaussian function, and optimizing the intensity of the Gaussian function of each of the multiple peaks, the diffraction angle of the peak top, and the full width at half maximum so that the sum of squared residuals obtained by summing the differences (residuals) between the intensity of the diffraction line and the sum of the intensities of each of the multiple peaks at each diffraction angle of the XRD figure for all diffraction angles is minimized.

[0217] Here, referring to the XRD pattern obtained by powder XRD measurement of the metal-supported catalyst in Example 1, we will explain the peak separation of the (111) diffraction line of a platinum-cobalt alloy having a peak top at a diffraction angle (2θ) around 40° (within the range of 39° to 44°).

[0218] In the XRD pattern of the metal-supported catalyst in Example 1, after baseline correction, a diffraction line with a peak top at a diffraction angle (2θ) of 40.6° appeared, as shown in Figure 5A. The shape of the middle portion of this diffraction line was significantly narrower than the shape of the lower portion, and the shape of the upper portion was even narrower than the shape of the middle portion. Therefore, it was considered that at least two diffraction lines overlapped at the peak at a diffraction angle (2θ) of 40.6°, including the diffraction line of a first Pt3Co with a relatively large full width at half maximum and the diffraction line of a second Pt3Co with a different crystallite size and a smaller full width at half maximum. Furthermore, since the metal-supported catalyst contains a carbon support, it was considered that a diffraction line originating from carbon was also included around a diffraction angle (2θ) of 43.5°.

[0219] Therefore, using the peak separation method described above, the diffraction line having a peak top at a diffraction angle (2θ) of 40.6° was separated into three components: a peak originating from the first Pt3Co, a peak originating from the second Pt3Co, and a peak originating from carbon.

[0220] The results of peak separation into these three components are shown in Figure 5B. In Figure 5B, the "Baseline Corrected" diffraction line is the diffraction line obtained by applying baseline correction to the diffraction line obtained by XRD measurement, and the "Pt3Co(1)" peak, the "Pt3Co(2)" peak, and the "Carbon" peak are the peaks derived from the first Pt3Co, the second Pt3Co, and the carbon, respectively, obtained by peak separation of the "Baseline Corrected" diffraction line.

[0221] However, as shown in Figure 5B, when the baseline-corrected diffraction lines were separated to match the broadening of the tail from around 35° to 39° of the diffraction angle (2θ) with the intensity up to the 80% mark of the peak, the sharpness of the peak top around 40.6° could not be reproduced.

[0222] In this regard, as described above, the diffraction line derived from the platinum-cobalt alloy represented by Pt3Co has a peak top at a position where the diffraction angle is 40.3° or more and less than 41.2°, so it was considered that the diffraction line of the third Pt3Co having a peak top at a position near 40.6° was mixed in.

[0223] Therefore, by the peak separation method described above, the diffraction line having a peak top at a position where the diffraction angle (2θ) is 40.6° was separated into four components composed of the peak derived from the first Pt3Co, the peak derived from the second Pt3Co, the peak derived from the third Pt3Co, and the peak derived from carbon.

[0224] The result of the peak separation into these four components is shown in FIG. 5C. Further, FIG. 5D shows an enlarged view of a part of FIG. 5C. In FIGS. 5C and 5D, the diffraction line after baseline correction indicates the diffraction line obtained by performing baseline correction on the diffraction line obtained by XRD measurement, and the peaks of "Pt3Co(1)", "Pt3Co(2)", "Pt3Co(3)", and "carbon" are respectively the peaks derived from the first Pt3Co, the second Pt3Co, the third Pt3Co, and the carbon obtained by peak separation of the diffraction line after the baseline correction.

[0225] Note that the peak obtained by adding the peaks of "Pt3Co(1)", "Pt3Co(2)", "Pt3Co(3)", and "carbon" almost completely coincides with the diffraction line after the baseline correction, so it is not shown in FIGS. 5C and 5D.

[0226] Thus, the sum of squared residuals in the case of peak separation into four components was reduced compared to the sum of squared residuals in the case of peak separation into three components and became an extremely small value. Therefore, it was concluded that the metal-supported catalyst of Example 2 carried the first Pt3Co particles, the second Pt3Co particles, and the third Pt3Co particles as platinum-cobalt alloy particles.

[0227] The crystallite sizes of the first, second, and third Pt3Co particles were then calculated using Scherrer's equation: crystallite size (nm) = Kλ / βcosθ. Here, in Scherrer's equation, K is Scherrer's constant (0.94), λ is the wavelength of the CuKα line (0.15418 nm), β is the full width at half maximum (radians), and θ is the diffraction angle (radians).

[0228] Specifically, for example, the crystallite size of the first Pt3Co particle was calculated by substituting the diffraction angle and full width at half maximum of the separated peak of "Pt3Co(1)" in the XRD figure shown in Figure 5C into Scherrer's formula. As a result, the crystallite size of the first Pt3Co particle was calculated to be 2.9 nm, the crystallite size of the second Pt3Co particle was calculated to be 3.4 nm, and the crystallite size of the third Pt3Co particle was calculated to be 10.7 nm.

[0229] Furthermore, the peak area percentage (%) of each of the three Pt3Co separation peaks obtained by the above-described peak separation (i.e., the peak area of ​​"Pt3Co(1)", the peak area of ​​"Pt3Co(2)", and the peak area of ​​"Pt3Co(3)") was calculated by dividing each peak area by the sum of the areas of the three Pt3Co separation peaks and multiplying by 100. As a result, the peak area percentage of the first Pt3Co particle was calculated to be 55.2%, the peak area percentage of the second Pt3Co particle was calculated to be 35.0%, and the peak area percentage of the third Pt3Co particle was calculated to be 9.8%.

[0230] Then, the volume-average particle diameter of the catalyst metal particles was calculated using a weighted average that utilized these peak area ratios as weights. Specifically, the volume-average particle diameter of the platinum alloy particles supported on the metal-supported catalyst in Example 2 was calculated to be 3.9 nm using the following formula: Volume-average particle diameter (nm) = {(2.9 × 55.2) + (3.4 × 35.0) + (10.7 × 9.8)} / (55.2 + 435.0 + 9.8).

[0231] Furthermore, "Peak area ratio / Crystallite size" 3The number-average particle diameter of the catalyst metal particles was calculated using a weighted average with "[ ]" as the weight. Specifically, the number-average particle diameter of the Pt3Co particles supported on the metal-supported catalyst in Example 2 was calculated to be 3.1 nm using the following formula: Number-average particle diameter (nm) = {(2.9 × 55.2 / 2.9 3 ) + (3.4 × 35.0 / 3.4 3 ) + (10.7 × 9.8 / 10.7 3 )} / (55.2 / 2.9 3 +35.0 / 3.4 3 +10.7 / 9.8 3 ).

[0232] Figure 6A shows the results of peak separation in the XRD pattern obtained for the metal-supported catalyst of Example C2. Figure 6B shows a magnified portion of the XRD pattern shown in Figure 6A. As shown in Figures 6A and 6B, the baseline-corrected diffraction lines were separated into a peak originating from one type of pure platinum, a peak originating from one type of platinum-cobalt alloy, and a peak originating from carbon.

[0233] In the XRD pattern obtained from powder XRD measurements of the metal-supported catalyst in Example C2, after baseline correction, diffraction lines with peaks at diffraction angles (2θ) of 39.7° and 41.0° appeared. The shape of the middle portion of each peak diffraction line was significantly narrower than the shape of the lower portion, and the shape of the upper portion was even narrower than the shape of the middle portion. Therefore, it was considered that three diffraction lines overlapped at the 39.7° peak: a diffraction line of a first Pt with a relatively large total width at half maximum, a diffraction line of a second Pt with a different crystallite size and a smaller total width at half maximum than the first Pt, and a diffraction line of a third Pt with a different crystallite size and an even smaller total width at half maximum than the first and second Pt. Furthermore, it was considered that three diffraction lines overlapped at the 41.0° peak: the diffraction line of the first Pt3Co with a relatively large full width at half maximum, the diffraction line of the second Pt3Co with a different crystallite size and smaller full width at half maximum, and the diffraction line of the third Pt3Co with a different crystallite size and even smaller full width at half maximum. In addition, since the metal-supported catalyst contains a carbon support, it was considered that it has a diffraction line of carbon origin at a diffraction angle (2θ) around 43.5°.

[0234] Therefore, as shown in Figures 6A and 6B, the diffraction lines having a peak top at a diffraction angle (2θ) of 39.7° and the diffraction lines having a peak top at a diffraction angle (2θ) of 40.1° were separated by the peak separation method described above into seven components consisting of a peak originating from the first Pt, a peak originating from the second Pt, a peak originating from the third Pt, a peak originating from the first Pt3Co, a peak originating from the second Pt3Co, a peak originating from the third Pt3Co, and a peak originating from carbon.

[0235] In Figures 6A and 6B, the "baseline-corrected" diffraction lines are those obtained by applying baseline correction to the diffraction lines obtained by XRD measurement. The peaks for "Pt(1)", "Pt(2)", "Pt(3)", "Pt3Co(1)", "Pt3Co(2)", "Pt3Co(3)", and "carbon" are the peaks derived from the first Pt, second Pt, third Pt, first Pt3Co, second Pt3Co, third Pt3Co, and carbon, respectively, obtained by peak separation of the "baseline-corrected" diffraction lines.

[0236] The crystallite sizes of the first Pt particle, the second Pt particle, and the third Pt particle, as well as the first Pt3Co particle, the second Pt3Co particle, and the third Pt3Co particle, were calculated using Scherrer's formula described above. For example, the crystallite size of the first Pt particle was calculated by substituting the diffraction angle and full width at half maximum of the separated peak of "Pt(1)" in the XRD figures shown in Figures 6A and 6B into Scherrer's formula. As a result, the crystallite size of the first Pt particle was calculated to be 3.7 nm, the crystallite size of the second Pt particle was calculated to be 8.1 nm, the crystallite size of the third Pt particle was calculated to be 18.7 nm, the crystallite size of the first Pt3Co particle was calculated to be 5.7 nm, the crystallite size of the second Pt3Co particle was calculated to be 18.6 nm, and the crystallite size of the third Pt3Co particle was calculated to be 29.5 nm.

[0237] Furthermore, the peak area percentage (%) for each of the three Pt and three Pt3Co particles obtained by the peak separation described above (i.e., the peak area of ​​"Pt(1)", the peak area of ​​"Pt(2)", and the peak area of ​​"Pt(3)", the peak area of ​​"Pt3Co(1)", the peak area of ​​"Pt3Co(2)", and the peak area of ​​"Pt3Co(3)") was calculated by dividing each of these peak areas by the sum of the peak areas of the three Pt and three Pt3Co particles and multiplying by 100. As a result, the peak area percentage of the first Pt particle was calculated to be 17.3%, the peak area percentage of the second Pt particle was calculated to be 44.4%, the peak area percentage of the third Pt particle was calculated to be 17.7%, the peak area percentage of the first Pt3Co particle was calculated to be 8.7%, the peak area percentage of the second Pt3Co particle was calculated to be 5.8%, and the peak area percentage of the third Pt3Co particle was calculated to be 6.1%.

[0238] Then, the volume-average particle diameter of the catalyst metal particles was calculated using a weighted average that utilized these peak area ratios as weights. Specifically, the volume-average particle diameter of the platinum alloy particles supported on the metal-supported catalyst in Example C2 was calculated to be 11.0 nm using the following formula: Volume-average particle diameter (nm) = {(3.7 × 17.3) + (8.1 × 44.4) + (18.7 × 17.7) + (5.7 × 8.7) + (18.6 × 5.8) + (29.5 × 6.1)} / (17.3 + 44.4 + 17.7 + 8.7 + 5.8 + 6.1).

[0239] Furthermore, "Peak area ratio / Crystallite size" 3 The number-average particle diameter of the catalyst metal particles was calculated using a weighted average with 3.7 × 17.3 as the weight. Specifically, the number-average particle diameter of the Pt3Co particles supported on the metal-supported catalyst of Example C2 was calculated to be 4.9 nm using the following formula: Number-average particle diameter (nm) = {(3.7 × 17.3 / 3.7 3 ) + (8.1 × 44.4 / 8.1 3 ) + (18.7 × 17.7 / 18.7 3 ) + (5.7 × 8.7 / 5.7 3 ) + (18.6 × 5.8 / 18.6 3) + (29.5 × 6.1 / 29.5 3 )} / (17.3 / 3.7 3 +44.4 / 8.1 3 +17.7 / 18.7 3 +8.7 / 5.7 3 +5.8 / 18.6 3 +6.1 / 29.5 3 ).

[0240] [ECSA sweep speed dependence] The electrochemical effective specific surface area (ECSA) (m²) of platinum contained in a metal-supported catalyst. 2 The concentration of Pt ( / g-Pt) was evaluated using the rotating ring disk electrode method with a rotating ring disk electrode device (RRDE-3A rotating ring disk electrode device ver.1.2, manufactured by BAS Corporation) and a dual electrochemical analyzer (CHI700C, manufactured by ALS Corporation).

[0241] Specifically, a triode rotating ring disk electrode device was first fabricated, having a working electrode containing a metal-supported catalyst. Specifically, a slurry was prepared by mixing 5 mg of the metal-supported catalyst with 50 μL of 5% Nafion® (Sigma-Aldrich, Nafion perfluorinated ion exchange resin, 5% solution (product number: 510211)), 400 μL of water, and 100 μL of isopropyl alcohol. Next, this slurry was subjected to sonication for 10 minutes, followed by homogenization for 2 minutes. The resulting slurry was then processed with a coating amount of metal-supported catalyst of 0.1 mg / cm². 2 To achieve this, the metal-supported catalyst was applied to a working electrode (RRDE-3A ring-disk electrode, platinum ring-gold disk electrode, disk diameter 4 mm, manufactured by BAS Corporation) and dried to produce a working electrode on which the metal-supported catalyst was supported.

[0242] A platinum electrode (Pt counter electrode 23 cm, manufactured by BAS Corporation) was used as the counter electrode, and a reversible hydrogen electrode (RHE) (accumulation-type reversible hydrogen electrode, manufactured by EC Frontier Corporation) was used as the reference electrode. In this way, a rotating ring disk electrode apparatus was obtained having a working electrode containing a metal-supported catalyst, a platinum electrode as the counter electrode, and a reversible hydrogen electrode (RHE) as the reference electrode. A 0.1 M perchloric acid aqueous solution was used as the electrolyte.

[0243] Then, ECSA was measured using the above-described rotating ring disk electrode apparatus. Specifically, cyclic voltammetry (CV) was performed in a nitrogen atmosphere using a three-electrode rotating ring disk electrode apparatus having a working electrode containing a metal-supported catalyst.

[0244] In the CV (Voltage Control) experiment, nitrogen bubbling was first performed for 10 minutes to remove oxygen from the electrolyte. Then, the current density was recorded as a function of potential during a potential sweep at a sweep rate of 10 mV / sec in the potential range from 0.0 V (vs. NHE) to 0.94 V (vs. NHE).

[0245] From the cyclic voltammogram obtained in this way, ECSA@10mV(m 2 We obtained the hydrogen adsorption charge (Q) from 0.0V (vs. NHE) to 0.4V (vs. NHE) during negative scanning in the cyclic voltammogram of the third cycle. Specifically, in the negative scanning, we obtained the hydrogen adsorption charge (Q) from 0.0V (vs. NHE) to 0.4V (vs. NHE). Hupd )(mC / cm 2 From ) the area-converted electrical charge (210 μC / cm²) 2 ) and platinum coating amount (L Pt )(mg-Pt / cm 2 Using the formula below, ECSA was calculated using equation (VI). JPEG2023129139000012.jpg15170

[0246] Similarly, ECSA@1000mV(m) at a sweep rate of 1000mV / sec 2The ratio of ECSA@10mV to ECSA@1000mV was calculated. Using the ECSA@10mV and ECSA@1000mV values ​​obtained in this way, the ECSA sweep rate dependence (%) of the metal-supported catalyst was calculated using the following equation (IV). Specifically, the value obtained by dividing ECSA@1000mV by ECSA@10mV was subtracted from 1, and the resulting value was multiplied by 100 to obtain the ECSA sweep rate dependence (%). JPEG2023129139000013.jpg17170

[0247] Figure 7 shows the results of evaluating the ECSA sweep rate dependence using the metal-supported catalyst of Example 1 and the metal-supported catalyst of Example C4. In Figure 7, the horizontal axis represents the sweep rate (mV / sec), and the vertical axis represents the ECSA maintenance rate (%). The ECSA maintenance rate was calculated by dividing the ECSA at each sweep rate by ECSA@10mV and multiplying the result by 100. That is, the value obtained by subtracting the ECSA maintenance rate (%) at a sweep rate of 1000mV / sec on the horizontal axis from 100 corresponds to the ECSA sweep rate dependence (%) described above.

[0248] As shown in Figure 7, when using the metal-supported catalyst of Example C4, the decrease in ECSA due to the increased sweep rate was smaller compared to when using the metal-supported catalyst of Example 1. Therefore, it was considered that in the metal-supported catalyst of Example C4, more catalyst metal particles were supported on the outside of the pores of the carbon support compared to the metal-supported catalyst of Example 1. In other words, since the metal-supported catalyst of Example C4 was manufactured by supporting catalyst metal particles on a carbon support by a liquid-phase reduction method, it was considered that these catalyst metal particles were preferentially supported on the outer surface of the carbon support.

[0249] [Performance evaluation of batteries having electrodes containing metal-supported catalysts] The performance of a fuel cell having a cathode containing a metal-supported catalyst was evaluated. Specifically, a battery cathode with a catalyst layer containing a metal-supported catalyst was first manufactured. That is, 0.25 g of metal-supported catalyst was added to an amount of electrolyte (equivalent mass EW = 820) with a weight ratio of 1.1 to the carbon support, and then 2 g each of distilled water and 1-propanol were added to prepare an electrolyte solution. This electrolyte solution and 25 g of balls were placed in a pot and mixed in a ball mill at 200 rpm for 50 minutes to obtain a slurry-like catalyst layer composition containing the metal-supported catalyst, which was uniformly dispersed.

[0250] The obtained slurry-like catalyst layer composition was spread over an area of ​​5 cm² on a gas diffusion layer ("29BC", manufactured by SGL Carbon) (2.3 cm × 2.3 cm). 2 In this region, the platinum content per unit area of ​​the battery electrode is 0.2 (mg-Pt / cm²). 2 A catalyst layer was formed on the gas diffusion layer by applying it in such a manner and allowing it to dry. In this way, a battery electrode was obtained in which a catalyst layer containing a metal-supported catalyst was formed.

[0251] Next, a fuel cell was manufactured that included a battery electrode having a catalyst layer containing a metal-supported catalyst. Specifically, the battery electrode containing the catalyst layer (positive electrode catalyst layer) manufactured as described above was used as the positive electrode.

[0252] On the other hand, the negative electrode was prepared as follows: 0.5 g of a commercially available platinum-supported catalyst (Pt / C) (UNPC40-II, manufactured by Ishifuku Metal Industries Co., Ltd.) containing platinum particles supported on a carbon support, 10 g of 5% Nafion®, 2 g of distilled water, and 25 g of balls were placed in a pot and mixed in a ball mill at 200 rpm for 50 minutes to prepare a slurry-like Pt / C composition. This slurry-like Pt / C composition was then subjected to a gas diffusion layer (5 cm 2 ) The platinum content per unit area is 0.1 (mg-Pt / cm²) 2 A negative electrode was fabricated in the same manner as the positive electrode described above, except that it was made to be such that the following was the case. The negative electrode included a catalyst layer (negative electrode catalyst layer) formed from the Pt / C composition.

[0253] Then, a solid polymer electrolyte membrane (Dupont, "NAFION® 211") was placed between the positive electrode catalyst layer and the negative electrode catalyst layer, and these were pressed together for 3 minutes at 150°C and 1 MPa to produce a MEA. A pair of gaskets were attached to this MEA, and then sandwiched between a pair of separators to produce a fuel cell single cell. Subsequently, the single cell produced as described above was installed in a fuel cell automatic evaluation system (Toyo Technica Co., Ltd.), and a power generation test was first performed, followed by a durability test.

[0254] The power generation test involved supplying saturated humidified air (oxygen) at a back pressure of 150 kPa to the positive electrode side at a rate of 2.5 L / min (relative humidity 100%), and saturated humidified hydrogen at a rate of 1.0 L / min (relative humidity 100%) to the negative electrode side. The cell temperature was set to 75°C, and the open-circuit voltage was measured for 5 minutes. Subsequently, the cell current density was measured at 4.0 A / cm². 2 From 0 A / cm 2 The cell voltage was measured after holding each current density for 3 minutes.

[0255] Furthermore, the output characteristics include a current density of 2.5 A / cm². 2 The voltage (mV) at this point was measured. Furthermore, the catalytic activity was measured at a current density of 0.2 A / cm². 2 The voltage (mV) at this point was measured. Additionally, the voltage at the start of the startup / shutdown test was recorded as a current density of 1.0 A / cm². 2 The voltage (mV) at that point was recorded.

[0256] Next, a start-up and shutdown test was conducted. Specifically, the cell temperature was set to 80°C, saturated humidified nitrogen was supplied to both sides of the single cell at a back pressure of 35 kPa at a rate of 1.0 L / min (relative humidity 100%), saturated humidified hydrogen was supplied to the anode side at a rate of 1.0 mL / min (relative humidity 100%), and the start-up and shutdown test was performed by repeatedly running a triangular wave cycle scanning the potential from 1.0 V to 1.5 V at a sweep rate of 500 mV / sec.

[0257] After performing the above triangular wave cycle 1000 times, the power generation test was performed again, and the output after the start-stop test was 1.0 A / cm. 2The voltage (mV) was recorded. Furthermore, the initial performance of 1.0 A / cm² was measured during the power generation test before the start-up / shutdown test. 2 From the voltage (mV) at that point, the power generation rate of 1.0 A / cm² measured in the power generation test after the start-stop test was obtained. 2 The voltage loss (mV), obtained by subtracting the voltage (mV) at the point of failure (voltage (mV) after 1000 cycles (mV)), was used as an indicator of durability in the first start-up / shutdown test.

[0258] Furthermore, a load fluctuation test was also conducted. Specifically, similar to the start-up and stop-down test described above, the voltage at the start of the load fluctuation test was set to a current density of 1.0 A / cm². 2 The voltage (mV) was recorded. Subsequently, the cell temperature was set to 75°C, saturated humidified nitrogen was supplied to both sides of the single cell at a back pressure of 150kPa at a rate of 0.5L / min (relative humidity 100%), and saturated humidified hydrogen was supplied to the anode side at a rate of 0.5mL / min (relative humidity 100%). A load fluctuation test was then performed by repeating a square wave cycle in which the potential was first held at 0.6V for 10 seconds, and then at 0.95V for 10 seconds.

[0259] After performing the above square wave cycle 10,000 times, the power generation test was performed again, and the current density after the load fluctuation test was 1.0 A / cm². 2 The voltage (mV) was recorded. Furthermore, the initial performance of 1.0 A / cm² was measured during the power generation test prior to the load fluctuation test. 2 From the voltage (mV) at that point, the 1.0 A / cm² measured in the power generation test after the load fluctuation test was obtained. 2 The voltage loss (mV), obtained by subtracting the voltage (mV) at the point of origin (voltage (mV) after 10,000 cycles (mV)), was used as an indicator of durability in load fluctuation tests.

[0260] [Evaluation of ionic resistance] Impedance measurements were performed by setting the cell temperature to 80°C, supplying saturated humidified nitrogen at a rate of 0.5 L / min with a back pressure of 35 kPa to both sides of a single cell (relative humidity 100%), and supplying saturated humidified hydrogen at a rate of 0.5 mL / min to the anode side (relative humidity 100%), and measuring the open-circuit voltage for 10 minutes. Subsequently, measurements were performed using an electrochemical measurement system (VSP-300, BioLogic) with an applied voltage of 450 mV, a measurement frequency of 20 kHz to 50 mHz, and an amplitude voltage of ±10 mV.

[0261] By fitting the Nyquist plot of the measured values ​​obtained from the measurement using ZView equivalent circuit analysis software (Scribner Associates), the ion resistance R is calculated. i They sought it.

[0262] The electrode state under the above measurement conditions can be modeled by the equivalent circuit shown in Figure 8A. In this equivalent circuit, L is the inductance originating from the wiring, etc., and R c R is the resistance of the electrolyte membrane or electrode component. sh is the short-circuit resistance, and W DeLevie is the Warburg impedance. In this case, the Warburg impedance Z is w This is expressed by the following equation (VII). JPEG2023129139000014.jpg12170

[0263] Here, in equation (VII) above, T is the time constant, and R i and C dl It is defined as the product of R. i ionic resistance (mΩ·cm) 2 ) and C dl ω is the electrical double-layer capacitance (F). ω is the frequency (Hz). j is the imaginary unit.

[0264] By fitting the Nyquist plot of the measured values ​​using the equivalent circuit shown in Figure 8A, R iThe following was calculated (Reference: Journal of The Electrochemical Society, 157 (3) B425-B436 (2010)). i This resistance is mainly due to the ionic resistance of the catalyst layer, and it is thought that this ionic resistance is influenced by the thickness of the catalyst layer, the hydrophilicity of the catalyst layer, and the degree of degradation of the ionomer.

[0265] Figure 8B shows the measured values ​​and fitting results of the Nyquist plot obtained for Example 1. The fitting results show the ion resistance R i It is 54 mΩ·cm 2 That was the case.

[0266] [result] Figure 9A shows the manufacturing conditions for the metal-supported catalysts of Examples 1-10 and Examples C1-C4, and the results of evaluating the characteristics of fuel cells containing these metal-supported catalysts.

[0267] As mentioned above, the start-up and shutdown tests were conducted at a relatively high potential of 1.0V to 1.5V for durability testing. Within this potential range, degradation due to oxidation of the carbon support is more likely to occur. Therefore, a smaller voltage loss during the start-up and shutdown tests indicates higher durability of the metal-supported catalyst.

[0268] In this regard, according to the voltage loss in the start-up / stop-down test shown in Figure 9A, the durability of the metal-supported catalysts in Examples 1-10 was about the same as that of Examples C1-C4, but the durability of the metal-supported catalysts in Examples 1-3 and 5-10 was superior to that of Example 4.

[0269] As mentioned above, durability tests were conducted at relatively low potentials of 0.6V and 0.95V during the load fluctuation test. Within this potential range, degradation of catalyst metal particles supported on the carbon support (e.g., aggregation and / or dissolution) is likely to occur. Therefore, a smaller voltage loss during the load fluctuation test indicates higher durability of the metal-supported catalyst.

[0270] In this regard, according to the voltage loss in the load fluctuation test shown in Figure 9A, the durability of the metal-supported catalysts in Examples 1 to 10 was superior to that of Examples C3 and C4, and comparable to that of Examples C1 and C2. Furthermore, in the load fluctuation test, the durability of the metal-supported catalysts in Examples 1, 2, and 4 to 10 was superior to that of Example 3.

[0271] The current density of 2.5 A / cm² shows the output characteristics of the metal-supported catalyst. 2 A higher voltage (mV) indicates that the output characteristics of the metal-supported catalyst are superior. Specifically, 2.0 A / cm² is a good value. 2 In the high current density region described above, a large amount of water is generated, which fills the pores of the carbon support, hindering mass transport and resulting in a decrease in the battery's voltage performance.

[0272] In this regard, according to Figure 9A, the power characteristics of the metal-supported catalysts in Examples 1-10 were similar to those of Examples C1-C4, but the power characteristics of Examples 1-3 and 5-8 were superior to those of Examples 4, 9, and 10, and the power characteristics of Examples 1, 2, and 5-8 were superior to those of Example 3.

[0273] Current density of 0.2 A / cm² indicates catalytic activity of the metal-supported catalyst. 2 The voltage (mV) in this region indicates that a higher value indicates better catalytic activity of the metal-supported catalyst. In other words, the overpotential of a fuel cell is classified into activation overpotential, resistance overpotential, and diffusion overpotential, but in the low current density region of 0.2 A / cm² 2 Therefore, because the effects of resistive overpotential and diffusion overpotential are small, it is suitable for evaluating catalytic activity.

[0274] In this regard, according to Figure 9A, the catalytic activity of the metal-supported catalysts in Examples 1-10 was comparable to that of Examples C1-C4, but the catalytic activity of Examples 1, 2 and 6-8 was superior to that of Examples 3-5, 9 and 10.

[0275] A lower ion resistance value indicates higher proton conductivity in the catalyst layer. Ion resistance is thought to be affected by factors such as the thickness of the catalyst layer, the hydrophilicity of the catalyst layer, and the degree of ionomer degradation. In catalyst layers containing metal-supported catalysts, low ion resistance is preferable. In this regard, as shown in Figure 9A, the ion resistance of the metal-supported catalysts in Examples 1-10 was lower than that of Examples C1-C4.

[0276] Figure 9B shows the results of evaluating the properties of the metal-supported catalysts in each example. The metal-supported catalysts in Examples 1 to 10 had similar Raman 2D / G ratios, Raman D half-width at half maximum, average pore diameter, and BET specific surface area as those in Examples C1 to C4.

[0277] Regarding the platinum content, the metal-supported catalysts in Examples 1-10 had a higher platinum content than that of Example C1, and a similar platinum content to that of Examples C2-C4. Regarding the platinum / non-platinum metal (Pt / M) molar ratio, the metal-supported catalysts in Examples 1-10 had a platinum / non-platinum metal molar ratio similar to that of Examples C1-C4.

[0278] Regarding alloy heterogeneity, the metal-supported catalysts of Examples 1-10 exhibited less alloy heterogeneity than those of Examples C2-C4, and the metal-supported catalysts of Examples 1-3 and 5-10 exhibited less alloy heterogeneity than those of Example 4.

[0279] Regarding half-value asymmetry, the metal-supported catalysts of Examples 1-10 had less half-value asymmetry than that of Example C4, the metal-supported catalysts of Examples 1-3 and 5-10 had less alloy heterogeneity than that of Example 4, and the metal-supported catalysts of Examples 1, 2, 5-8 and 10 had less alloy heterogeneity than that of Examples 3 and 9.

[0280] Regarding the 1 / 4 value asymmetry, the metal-supported catalysts in Examples 1-10 had a smaller 1 / 4 value asymmetry than those in Examples C2-C4, the metal-supported catalysts in Examples 1, 3, 5 and 7-10 had a smaller 1 / 4 value asymmetry than those in Examples 2, 4 and 6, and the metal-supported catalysts in Examples 1, 5, 7, 8 and 10 had a smaller 1 / 4 value asymmetry than those in Examples 3 and 9.

[0281] Regarding the number-average particle size of the catalyst metal particles, the metal-supported catalysts in Examples 1 to 10 had a number-average particle size similar to that of Examples C1 to C4, while the metal-supported catalysts in Examples 1 to 8 had a smaller number-average particle size than those in Examples 9 and 10, and the metal-supported catalysts in Examples 1, 2, and 5 to 8 had a smaller number-average particle size than those in Examples 3 and 4.

[0282] Regarding the volume-average particle diameter of the catalyst metal particles, the metal-supported catalysts in Examples 1-10 had a volume-average particle diameter similar to that of Examples C1-C3 and smaller than that of Example C4. The metal-supported catalysts in Examples 1-8 had a number-average particle diameter smaller than that of Examples 9 and 10. The metal-supported catalysts in Examples 1, 2, and 5-8 had a number-average particle diameter smaller than that of Examples 3 and 4.

[0283] Regarding the ECSA sweep rate dependence, the metal-supported catalysts of Examples 1-10 had a similar ECSA sweep rate dependence to that of Examples C1-C4, while the metal-supported catalysts of Examples 1-9 had a greater ECSA sweep rate dependence than that of Example 10, and the metal-supported catalysts of Examples 1, 2, and 5-8 had a greater ECSA sweep rate dependence than that of Examples 3, 4, and 9.

Claims

1. A carbon support; catalytic metal particles, which include a precious metal alloy, supported on the carbon support; A metal supported catalyst comprising: The ratio of the weight of the precious metal to the weight of the metal-supported catalyst is 35% by weight or more; The following characteristics (a) and / or (b): (a) an alloy composition non-uniformity calculated by the following formula (I) of 0.55 or less; (In the above formula (I), the theoretical lattice constant and the measured lattice constant are the theoretical lattice constant and the measured lattice constant of the precious metal alloy, respectively.) (b) the half-value asymmetry and the quarter-value asymmetry calculated by the following formulas (II) and (III), respectively, are both 0.55 or less; (In the above formula (II) and formula (III), D m is the value of the diffraction angle 2θ at which the diffraction line shows maximum intensity in the range of diffraction angles 2θ at which the diffraction peak of the (111) plane of the precious metal alloy appears in the X-ray diffraction pattern obtained by powder X-ray diffraction, and D Lh is the smallest diffraction angle 2θ value among the diffraction angles 2θ at which the diffraction line shows half the maximum intensity in the above range, and D Hh is the largest diffraction angle 2θ value among the diffraction angles 2θ at which the diffraction line shows half the maximum intensity in the above range, and D Lq is the smallest diffraction angle 2θ value among the diffraction angles 2θ at which the diffraction line shows a quarter of the maximum intensity in the above range, and D Hq is the largest value of the diffraction angle 2θ among the diffraction angles 2θ at which the diffraction line shows a quarter of the maximum intensity in the above range.) A metal supported catalyst comprising:

2. Having the characteristic (a), The metal supported catalyst of claim 1.

3. The compound has the characteristic (b), The metal supported catalyst according to claim 1 or 2.

4. The number average particle diameter of the catalytic metal particles is 8.0 nm or less. The metal supported catalyst according to any one of claims 1 to 3.

5. The volume average particle diameter of the catalytic metal particles is 8.0 nm or less. The metal supported catalyst according to any one of claims 1 to 4.

6. The metal-supported catalyst according to any one of claims 1 to 5, electrode.

7. 7. The electrode according to claim 6, battery.

8. A carbon support; catalytic metal particles, which include a precious metal alloy, supported on the carbon support; The method for producing a metal supported catalyst according to any one of claims 1 to 5, comprising: a first impregnation step of impregnating the carbon support with a precursor of a first metal, which is one of a precious metal and a non-precious metal constituting the precious metal alloy; a first gas-phase reduction step of subjecting the carbon support impregnated with the precursor of the first metal to a gas-phase reduction treatment to obtain a first metal-supported catalyst carrying the first metal; a second impregnation step of impregnating the first metal supported catalyst with a precursor of a second metal, which is the other of the precious metal and the non-precious metal; a second gas-phase reduction step of subjecting the first metal-supported catalyst impregnated with the precursor of the second metal to a gas-phase reduction treatment and then to an alloying treatment to obtain a metal-supported catalyst on which catalytic metal particles containing an alloy of the first metal and the second metal are supported; A method for producing a metal supported catalyst comprising the steps of:

9. A carbon support; catalytic metal particles, which include a precious metal alloy, supported on the carbon support; A method for producing a metal supported catalyst comprising the steps of: a first impregnation step of impregnating the carbon support with a precursor of a first metal, which is one of a precious metal and a non-precious metal constituting the precious metal alloy; a first gas-phase reduction step of subjecting the carbon support impregnated with the precursor of the first metal to a gas-phase reduction treatment to obtain a first metal-supported catalyst carrying the first metal; a second impregnation step of impregnating the first metal supported catalyst with a precursor of a second metal, which is the other of the precious metal and the non-precious metal; a second gas-phase reduction step of subjecting the first metal-supported catalyst impregnated with the precursor of the second metal to a gas-phase reduction treatment and then to an alloying treatment to obtain a metal-supported catalyst on which catalytic metal particles containing an alloy of the first metal and the second metal are supported; Including, The first impregnation step comprises first maintaining a solution containing a precursor of the first metal and the carbon support under reduced pressure and then maintaining the solution under pressure; and / or The second impregnation step includes first holding a solution containing a precursor of the second metal and the first metal supported catalyst under reduced pressure and then holding the solution under pressure. A method for producing a metal supported catalyst.

10. A carbon support, catalytic metal particles, which include a precious metal alloy, supported on the carbon support; A method for producing a metal supported catalyst comprising the steps of: a first impregnation step of impregnating the carbon support with a precursor of a first metal, which is one of a precious metal and a non-precious metal constituting the precious metal alloy; a first gas-phase reduction step of subjecting the carbon support impregnated with the precursor of the first metal to a gas-phase reduction treatment to obtain a first metal-supported catalyst carrying the first metal; a second impregnation step of impregnating the first metal supported catalyst with a precursor of a second metal, which is the other of the precious metal and the non-precious metal; a second gas-phase reduction step of subjecting the first metal-supported catalyst impregnated with the precursor of the second metal to a gas-phase reduction treatment and then to an alloying treatment to obtain a metal-supported catalyst on which catalytic metal particles containing an alloy of the first metal and the second metal are supported; Including, The first impregnation step comprises maintaining a solution containing a precursor of the first metal and the carbon support at a temperature of 5° C. or less; and / or The second impregnation step includes maintaining a solution containing a precursor of the second metal and the first metal supported catalyst at a temperature of 5° C. or less. A method for producing a metal supported catalyst.

11. The gas phase reduction treatment is a treatment of heating in a reducing atmosphere. The method for producing a supported metal catalyst according to any one of claims 8 to 10.

12. The first impregnation step comprises maintaining a solution containing a precursor of the first metal and the carbon support under reduced pressure; and / or The second impregnation step includes maintaining a solution containing a precursor of the second metal and the first metal supported catalyst under reduced pressure. The method for producing a supported metal catalyst according to claim 8, 10 or 11.

13. The first impregnation step comprises maintaining a solution containing a precursor of the first metal and the carbon support under pressure; and / or The second impregnation step includes holding a solution containing a precursor of the second metal and the first metal supported catalyst under pressure. The method for producing a supported metal catalyst according to claim 8, 10 or 11.

14. The first impregnation step comprises first maintaining a solution containing a precursor of the first metal and the carbon support under reduced pressure and then maintaining the solution under pressure; and / or The second impregnation step includes first holding a solution containing a precursor of the second metal and the first metal supported catalyst under reduced pressure and then holding the solution under pressure. The method for producing a supported metal catalyst according to claim 8, 10 or 11.

15. The first impregnation step comprises maintaining a solution containing a precursor of the first metal and the carbon support at a temperature of 5° C. or less; and / or The second impregnation step includes maintaining a solution containing a precursor of the second metal and the first metal supported catalyst at a temperature of 5° C. or less. The method for producing a supported metal catalyst according to any one of claims 8, 9, 11 to 14.